GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2019)
A dataset containing 887514624 species occurrences available in GBIF matching the query: BasisOfRecord: Observation or Machine Observation or Human Observation or Material sample or Literature Occurrence or Specimen or Fossil or Living Specimen Country: United States of America or Sweden or Canada or Netherlands or Denmark or Norway or Brazil or United Kingdom or Belgium or Germany or Iran, Islamic Republic of or Iraq or France or Finland or Estonia or New Zealand or Svalbard and Jan Mayen or Mexico or Colombia or Japan or Belize or Iceland or Spain or Russian Federation or Portugal or Ireland or South Africa or Australia or French Southern Territories or Peru or Jersey or Angola or Hungary or Ecuador or Argentina or Bermuda or Afghanistan or Isle of Man or Mozambique or Honduras or Costa Rica or Luxembourg or Italy or Kenya or Congo, Democratic Republic of the or Panama or Austria or Venezuela, Bolivarian Republic of or Gambia Month: January or February or March or April or May or June or July or August or September or October or November or December Year: 1899-2019. The dataset includes 887514624 records from 11787 constituent datasets: 9 records from Revision of the Australian leaf beetle genus Cheiloxena Baly, 1860 (Coleoptera: Chrysomelidae: Spilopyrinae). 1 records from Nomenclatural and type catalogue of Athoracophoridae (Mollusca: Eupulmonata: Succineoidea): a synopsis of the first 185 years of biodiscovery in the South West Pacific region. 2177 records from Polychaetes in surface sediments off Sylt collected during HEINCKE cruise HE241. 505 records from KUBI Paleobotany Collection. 158 records from Waldstück Bremerhagen LK Bio Kl. 12. 2 records from Stomatopod Crustacea of the Austral and Gambier Islands, French Polynesia. 235 records from Estimación de la densidad poblacional y dieta del lince (Lynx rufus) Sierra Seri, Sonora y Janos, Chihuahua. 225517 records from Canadian Museum of Nature Herbarium. 808 records from Banco de Germoplasma del Real Jardín Botánico Juan Carlos I. 561 records from Range table from benthic foraminifers in ODP Hole 146-889A. 43620 records from Insect specimens in the Museum of Nature and Human Activities, Hyogo Prefecture, Japan. 1971 records from Estudio florístico de los bosques mesófilos de la Sierra Mazateca de Oaxaca, México. 314 records from Tejidos colectados en la ventana de biodiversidad del Complejo Cenagoso de Zapatosa, Municipio de Chimichagua, Cesar, Colombia.. 371 records from Bannwald Burghauser Forst. 93 records from Données Cétacés Transmed. 240 records from Données des collections de cnidaires du MNHN. 10 records from New Species and Records of Costa Rican Featherwing Beetles (Coleoptera: Ptiliidae). 80 records from (Table 3) Relative abundances of palynoclasts, palynomorphs and microplankton in ODP Leg 112 samples. 2726 records from ZUEC-OPH - Coleção de Ophiuroidea do Museu de Zoologia da UNICAMP. 176 records from Invasive Non-native species data in the Clyde catchment, collated by Central Scotland Forest Trust. 14 records from Revision of Lutnes Cameron (Hymenoptera: Eupelmidae). 5238 records from Naturalis Biodiversity Center (NL) - Amphibia and Reptilia. 20 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 655 records from COA Bird Collection (Arctos). 5 records from Schulhof Montessori Schule (Rotenburg / Wümme). 111225 records from New Zealand Arthropod Collection (NZAC). 69 records from Range table from planktonic foraminifers in ODP Hole 151-910A. 3976 records from Mise en place d'un suivi scientifique des odonates pour la production d’indicateurs de biodiversité. 154 records from Sorensen distance for herbivores. 89 records from Great British Bee Count 2016 - Stage 2 (records verified from photo). 16 records from Three new species of Miroculis from the Serra da Mocidade National Park, Roraima State, Brazil, with new records and checklist of the Leptophlebiidae (Ephemeroptera). 10499 records from Bryophyte specimens of The Nagoya University Museum. 3896 records from University of Guam Insect Collection. 18156 records from National Botanic Garden Belgium - Myxomycetes. 151 records from Monocotiledóneas del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 102 records from Birdrace-Die_Nachtraben-Stuttgart. 174 records from Artenvielfalt des "Grünen Klassenzimmers". 2114 records from Museu de Ciències Naturals de Barcelona: BGJBB. 42 records from Great British Bee Count 2015 - Stage 2 (records verified from photo). 194 records from Planktic foraminifera counts at CTD station M39/4_357CTD-15. 8 records from Revision of the shore-fly genus Peltopsilopa Hendel (Diptera: Ephydridae). 177 records from Meiobenthic taxon counts from deep-sea in situ recolonization experiment I deployed at station PS64/474-1 during ARK-XIX/3c. 54 records from Waldsee. 148701 records from Sustainable Rivers Audit. 11424 records from Inventario florístico y entomofaunístico en tres objetos de conservación ecosistémicos en las zonas núcleo de las reservas estatales de Balam-kú y Balam-kin, Campeche. 41 records from Liether Park (LMS), 6c. 2505 records from ZUEC-ORT - Coleção de Orthoptera do Museu de Zoologia da UNICAMP. 1 records from Redescription of four species of Cytaea Keyserling, 1882 (Araneae: Salticidae). 2 records from New species of Simothraulopsis Demoulin, 1966 (Ephemeroptera: Leptophlebiidae) from Northeastern Region of Brazil. 1044366 records from Belgian IFBL Flora Checklists (1939-1971). 494 records from (Table 5) Distribution of calcareous nannofossil species at DSDP Hole 40-361. 149 records from Benthic foraminiferal assemblage (Rose Bengal stained) in MUC SC1-K, size fraction >150 µm. 104 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1c. 115 records from Range table from planktonic foraminifers in ODP Hole 155-942C. 821 records from Bird specimens of Saitama Museum of Natural History. 2247405 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA). 63 records from Phytoplankton abundance in surface water in 2000, Ancon, Peru. 413 records from (Fig. 5) Sea-surface temperature reconstructions of sediment core MD99-2304. 53 records from Total foraminifera counts of multinet M21/5_MSN735. 618 records from Mycology collection, Norwegian Forest and Landscape Institute. 18 records from Amazoonops, a new genus of goblin spiders (Araneae: Oonopidae) from the Brazilian Amazon. 1 records from A third species in the rare Australian ant genus Peronomyrmex Viehmeyer (Hymenoptera: Formicidae).. 988 records from flower availability 2008 Alb-korrigiert. 9481 records from Plant specimens of Tama City Cultural Foundation. 2808 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 2 records from Neoclita pringlei (Scarabaeidae, Cetoniinae), a new relict genus and species from the Drakensberg Range of South Africa. 8 records from A new species of the genus Bertholdia Schaus, 1896 (Lepidoptera: Erebidae: Arctiinae) from the Neotropical region: Bertholdia zoenia sp. n.. 37 records from New distribution data for some charismatic tramp species of Platygastroidea (Hymenoptera). 18 records from Revision of the Australian Union-Jack wolf spiders, genus Tasmanicosa (Araneae, Lycosidae, Lycosinae). 93 records from Poliquetos (Annelida: Polychaeta) del Pacífico Mexicano. 237 records from Range table from benthic foraminifers in ODP Hole 161-974B. 1904 records from Escarabajos coprófagos de la cuenca alta y media del río Bita, Vichada (Colombia). 69 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from POSEIDON cruise 334. 4 records from UWIZM Anoles. 2845 records from Pat Livermore's Fungus Records 1976 - 2000. 5 records from Three new species of Cladorhiza (Demospongiae, Poecilosclerida, Cladorhizidae) from the Northeast Pacific Ocean. 5 records from New species and new geographical record of Ochrotrichia Mosely 1934 (Trichoptera: Hydroptilidae) from Rio de Janeiro state, Brazil. 444 records from Pollen analysis of sediment profile TR0 from Truennensee. 2451 records from Macrobenthos Chukchi Sea, 1986. 1 records from The genus Acantholyda (Hymenoptera, Pamphiliidae) of Japan: A revised key and a description of the previously unknown female of Acantholyda flaviventris. 21 records from Abundance of benthos infauna at station GIK23004-3. 208 records from Condamine Alliance. 2 records from Tobrilus methanus sp. n. and Tripyla posolskii sp. n. (Nematoda, Triplonchida) from Lake Baikal, Russia. 586 records from Inventario taxonómico de los hongos conidales saprobios del parque Yumka' en Villahermosa, Tabasco. 825 records from Small rodents in mountain birch forest 2002-2016. 4742 records from Sistema Arrecifal Veracruzano: condición actual y programa permanente de monitoreo: Primera Etapa. 139 records from (Table A.04) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 7 (80-150 µm). 4 records from Proctolaelaps species (Acari: Mesostigmata: Melicharidae) from Egypt, with description of a new species and complementary descriptions of other five species. 1 records from Conservación de la población de Loro Orejiamarillo (Ognorhynchus icterotis) en el piedemonte llanero, departamento del Meta. 422 records from Station de Biologie des Laurentides de l'Université de Montréal - Collection Ornithologique. 682 records from St Andrews BioBlitz 2015. 15 records from Tardigrad collection of the National Museum of Nature and Science. 181 records from Análisis del ictioplancton del ecosistema costero de Celestún, Yucatán, México. 4 records from Two new species of Mendozellus Linnavuori (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) with redescription of Mendozellus asunctia Cheng. 13529 records from sarce_rockyshores. 1701 records from (Table 12B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-590B. 420 records from Phytoplankton abundance in surface water in October 1995, Ilo, Peru. 18 records from Naturtag. 20463 records from Herbier Louis-Marie (QFA) - Collection de lichens. 2160 records from EDP Foz Tua: Bat Habitats - Complementary Studies [2010]. 1346 records from Actualización de la Colección de Microorganismos de importancia acuática. 2 records from Morphology and molecules say: Tanytarsus latens, sp. nov. from Finland (Diptera: Chironomidae). 165061 records from Oiseaux nicheurs de France métropolitaine 2009-2012 - Nidification probable. 2 records from Revisions of two poorly known species of Opisthotropis Günther, 1872 (Squamata: Colubridae: Natricinae) with description of a new species from China. 204 records from Planktic foraminifera abundance of Hole 29-284A. 73 records from Planktic foraminifera abundance of Hole 49-409. 847 records from Plant. 39 records from Grasses of the Forest Herbarium Ibadan (FHI) Nigeria. 3 records from New species of Dispio Hartman, 1951 and Streblospio Webster, 1879 (Polychaeta, Spionidae) from the coast of the Iberian Peninsula. 4 records from The crane fly genus Libnotes Westwood, 1876 (Diptera: Limoniidae) for Korea including two new species and an identification key. 1551 records from (Table 1) Range chart for planktonic foraminifers from ODP Hole 111-667A. 774 records from Biodiversidad ictica de la Isla Cayo Serranilla Expedición Seaflower 2017 proyecto Colombia BIO. 1001 records from Colecção Entomológica IIA. 49 records from Equinodermos de las unidades ecológicas someras Expedición Seaflower Serranilla2017 - Proyecto Colombia BIO. 558 records from Herbarium WRSL, Main Collection. 707 records from Planktic foraminifera abundance of Hole 49-408. 330 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE236. 3307 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 6 records from Rango, comportamiento, tamaño de población y conservación de felinos en el Volcán de Colima. 4351 records from University of Alberta Freshwater Invertebrate Collection (UAFIC). 87 records from Nannofossil abundance of Hole 10-91. 36 records from Range table from benthic foraminifers in ODP Hole 181-1119C. 4482 records from DMNS Egg Collection (Arctos). 66 records from (Table 9) Distribution of ostracode species in surface sediments of the southern Laptev Sea. 8 records from A new genus and species of Haplobainosomatidae (Diplopoda: Chordeumatida) from the MSS of the Sierra de Guadarrama National Park, central Spain. 14817 records from Lepidopterous specimens of Yamagata Prefectural Museum. 662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 7327 records from Helgeland Museum, Lepidoptera. 482 records from Pez León en Venezuela. 1142 records from (Table 8) Distribution of planktonic foraminifera in the late Cretaceous and Eocene to early Miocene sections of ODP Hole 149-899B. 1 records from Mites of the genus Malaconothrus (Acari: Cryptostigmata) from the British Isles. 54 records from Taxonomy of Morellia Robineau-Desvoidy (Diptera: Muscidae): revision of the subgenera Morellia s. str. and Parapyrellia Townsend. 1226 records from Museu Paraense Emílio Goeldi - Chelonia Collection. 238 records from Range table from benthic foraminifers in ODP Hole 181-1122C. 77 records from Helechos del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO. 3718 records from (Table 3) Relative abundance of benthic foraminifera in late Cenozoic sediments of DSDP Hole 68-502A from the Caribbean Sea. 1527 records from Données naturalistes de Quentin ROME. 113 records from SEWBReC Springtails and allies (South East Wales). 16 records from Unraveling the white-clothed Diestostemma Amyot & Serville: a taxonomic revision of the American sharpshooters of the D. bituberculatum complex (Hemiptera: Cicadellidae). 6 records from Three new brackish-water thalassocypridine species (Crustacea: Ostracoda: Paracyprididae) from the Ryukyu Islands, southwestern Japan. 424 records from (Table 5) Distribution of planktonic foraminifers in ODP Hole 112-683B. 361 records from Range table from benthic foraminifers in ODP Hole 172-1054B. 855 records from Insectos recolectados en trampas Malaise en el departamento de Santander - Proyecto Colombia Bio. 97 records from BIRDRACE NABUhu Trier!. 108 records from Benthic foraminifera abundance in ODP Leg 155 holes. 7839 records from UK Biodiversity Action Plan Invertebrate Data for Wales. 599 records from Farmland bird database in Dumfries and Galloway, 1999-2011. 1655 records from InsectScale2008FlowerCover. 248 records from Plants galls. 12824 records from The Himalayan Uplands Plant database (HUP Version 1). 130 records from Artenvielfalt auf dem Schulgelände. 1739 records from Range table from planktonic foraminifers in ODP Hole 157-953C. 174 records from Nannofossil abundance of Hole 64-479. 47769 records from DMNH Birds. 16 records from Eupithecia gypsophilata, a new species in the graphata species group of the genus Eupithecia Curtis (Lepidoptera, Geometridae, Larentiinae). 1016 records from Dead benthic foraminifera in South Atlantic surface sediments. 69 records from BIRDRACE Pfeifenten. 1 records from Enneophyllus ecarina, a new species of scaphopod shell dwelling hermit crab (Crustacea: Decapoda: Anomura: Paguridae) from deep-sea off the Ryukyu Islands, southern Japan. 11 records from Ephemeroptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 44088 records from Insects from light trap (1992–2009), rooftop Zoological Museum, Copenhagen. 15 records from Description of lithologic section units of IODP Hole 325-M0036A. 17 records from Collections ichtyologiques et herpétologiques (BOUM). 119 records from (Table 11) Dinoflagellate cyst species distribution in ODP Hole 112-687B. 288 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 298 records from DBRC Austropotamobius pallipes records 1960 - 2015. 15029 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 8516 records from Données naturalistes de Bruno OGER. 112 records from La collection Gilles Becquet (BOUM). 65385 records from Norwegian Lepidoptera working group. 20 records from Five new species and novel descriptions of opposed sexes of four species of the spider genus Attacobius (Araneae: Corinnidae). 780 records from Distribution of agglutinated foraminifers in sediment core Well 6406/8-1. 37997 records from Pteridophyta collection of Museum of Natural and Environmental History, Shizuoka. 66 records from Range table from benthic foraminifers in ODP Hole 139-855B. 267 records from Dierloch, nördlicher Mooswald (Freiburg-Hochdorf). 385 records from (Table 2d) Nannofossil distribution chart of petroleum well Great-Eastern-1. 274 records from BIRDRACE Asiola-Quartett. 54 records from NE Scotland fish records 1800-2010. 565 records from Relative abundance of planktic foraminifera in sediment core RC17-69. 20137 records from SEWBReC Bees, Wasps and Ants (South East Wales). 12 records from Flora und Fauna am Mühlberg. 9042 records from Northern Biodiversity Program Coleoptera (2010-2011). 217 records from Birdrace-Ornis_im_Einsatz-Lahn-Dill-Kreis. 10 records from Systematic notes on some leptomedusa species with a description of Neotima galeai n. spec. (Hydrozoa, Cnidaria). 624 records from (Table 2) Distribution of benthic foraminifera in the Cretaceous succession of DSDP Hole 95-612. 10 records from Données naturalistes d'Olivier BARDET. 11 records from Neotropical osmylids (Neuroptera, Osmylidae): Three new species of Isostenosmylus Krüger, 1913, new distributional records, redescriptions, checklist and key for the Neotropical species. 28 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2446-2. 5 records from Sächsische Schweiz (Pfaffenstein). 578 records from Conservación de la tortuga caguama del Pacífico (Caretta caretta): protección dentro del hábitat crítico de alimentación y desarrollo en Baja California Sur. 1171 records from Glasaalmigratie - Glass eel migration in the river Yser. 1026 records from (Appendix D) Analyses of the benthic foraminifer assemblage at ODP Hole 112-680B. 1 records from Nemertean specimens of Ryukyu University Museum (Fujukan). 69 records from Naturpark Kottenforst-Ville 18.6.09. 111094 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 2208 records from Inventario florístico de Tetipac y sus alrededores (Sierra de Taxco). 14 records from Living Cirripedia. 45947 records from DDT05_2017_12_18. 2386 records from Centre for Genetic Resources, the Netherlands, Indigenous Trees and Shrubs. 14503 records from CCBER Herpetology Collection. 12 records from New species of Pseudoscorpiones (Arachnida) from tree hollows in a Mediterranean oak forest in Spain. 1031 records from ConDidact Citizen Science Surveys - Spiders 2011. 83 records from Roter Berg Werdau (Leubnitz). 14 records from Taxonomy and phylogeny of calcareous sponges (Porifera: Calcarea: Calcinea) from Brazilian mid-shelf and oceanic islands. 506 records from Base de datos sobre los hongos anamorfos de restos de vegetales del bosque mesófilo del estado de Veracruz. 9 records from Division of the genera Sparna Thomson, 1864 and Carterica Pascoe, 1858 (Coleoptera, Cerambycidae, Lamiinae, Colobotheini) with description of six new genera and eight new species. 64 records from Mauernacker (Wettsaasen). 3755 records from Données naturalistes de Charlotte PICARD. 6 records from A revision of the South American species of the ant genus Probolomyrmex (Hymenoptera: Formicidae).. 29 records from A new distinctive species of Barydesmus (Diplopoda, Polydesmida, Platyrhacidae) from Ecuador, with an annotated bibliographical checklist of the American Platyrhacidae. 92 records from Wiesen in der Grünen Mitte. 478 records from Culture Collection of Microalgae and Zygnematophyceae Collection Hamburg (MZCH-SVCK). 285 records from Loup 2014 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 1 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 163 records from Dinoflagellate cysts of ODP Hole 189-1172D. 57 records from CSIRO Yellow Box Fragmentation Project. 50312 records from Entomology Collection at the Natural History Museum of Utah. 1 records from A new species of Cladotanytarsus (Lenziella) from Oregon supports the systematic concept of the subgenus (Diptera: Chironomidae). 886 records from Inventarios florísticos en Baja California Sur (II): Vegetación costera. 2 records from Données naturalistes (Rhopalocères et Zygènes) de Nicolas JEAN (données récoltées en tant que bénévole). 1945 records from Registros biológicos de predios promocionados como Reservas Naturales de la Sociedad Civil-RNSC en el Cañón de Amaime, municipio El Cerrito, Valle del Cauca, Colombia.. 105119 records from ALCB - Herbário Alexandre Leal Costa. 165150 records from Australian National Insect Collection. 350 records from (Table T1) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1170D sediments. 114 records from BIRDRACE LiLaLau. 6 records from Herbarium specimens of Limoges university (LIMO). 2849 records from Biobanco de ADN Vegetal de la Universidad de Salamanca: SALA-DNA. 72350 records from Fish specimens of Kagoshima University Museum. 25858 records from RECORD Odonata Data. 137 records from SNH Invertebrate Site Condition Monitoring 2013/14: North Rothiemurchus Pinewood SSSI. 467 records from Diptera Collection of Museum and Institute of Zoology PAS. 4057 records from UTEP Invertebrates (Arctos). 59 records from Schulteich Freie Waldorfschule Darmstadt. 72 records from Ostfriesland. 1 records from Electrogena brulini sp. nov. and E. vipavensis Zurwerra & Tomka, 1986 syn. nov. revealed by integrative taxonomy of E. gridellii (Grandi, 1953) (Ephemeroptera: Heptageniidae). 684 records from Inventario de Flora de la Reserva Forestal Protectora Regional Cuchillas del Tigre, El Calón y La Osa. Municipios de San Francisco y Sonsón-Antioquia.. 9202 records from HUFSJ - Herbário da Universidade Federal de São João del-Rei. 292 records from Monitoreo y recolección de la diversidad de razas de maíz criollo en la región de la Huasteca en México para complementar las colecciones de los Bancos de germoplasma de INIFAP y CIMMYT. 476 records from Herbario MAIA, colección Flora Forestal del INIA-CIFOR. 2 records from A new deep-water species of Alpheopsis Coutière, 1897 from the Indo-West Pacific (Decapoda: Alpheidae). 56713 records from CGMS - Herbário da Fundação Universidade Federal de Mato Grosso do Sul. 4 records from Planktic foraminifera abundance of Hole 19-191A. 325 records from Diversidad genética del cultivo del chile (Capsicum spp) determinada por isoenzimas y RFLP's tipos: serrano, jalapeño, manzano y silvestres en su área de distribución. 1331 records from (Table 2) Distribution of planktic foraminifers of sediment core D11957P. 1221 records from Freshwater fish records via iRecord. 1536 records from Flora útil del Municipio de la Huerta, Jalisco. 1910 records from Chucki_Seaooplankton1953/4. 91 records from Range table from planktonic foraminifers in ODP Hole 146-892A. 7 records from Review of the New World genus Nanium Townes, 1967 (Hymenoptera: Ichneumonidae: Ctenopelmatinae), with two new species from the Neotropical region. 838 records from Phytoplankton abundance during Gunnar Thorson cruise GT90/5. 1905 records from Inventario y monitoreo del Canal de Infiernillo para el comanejo de los recursos marinos en el territorio Seri, Golfo de California. 3753 records from Vascular plants of Amrum 2007-2008. 25608 records from National Dormouse Database (NDD). 9 records from Records of pine martens from SNH casework reports and licence applications, 2005 - 2016. 26 records from Nannofossil abundance of Hole 10-93. 2193 records from Modelos predictivos de distribución geográfica para Spizella wortheni, Cynomys mexicanus, Vulpes macrotis zinseri y Taxidea taxus berlandieri. 4149 records from Temporal evolution of zooplankton by WP2 net in the Northwestern Mediterranean Sea, Villefranche-sur-mer 2004-2010.. 12 records from Art´n Vielfalt im Kinderwald. 263 records from Planktic foraminifera counts of sediment core V14-77. 251819 records from Phase 2 Lowland Grassland Survey of Wales. 95 records from Birdrace-Buteo1_DO-Dortmund. 78 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM2. 480 records from (Table 2) Distribution of calcareous nannoplankton in selected samples of ODP Site 112-679. 55 records from Fauna íctica del río Arquía, en las estribaciones del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 24163 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 645 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE293. 98 records from Distribution of planktonic foraminifera in DSDP Hole 90-594 east of New Zealand. 1285805 records from Données issues de Clicnat (Base de données naturaliste picarde gérée par Picardie Nature). 413272 records from DATAVES. 308 records from Ascomycetes of Russian Fennoscandia. 559 records from DATABASE OF FINDS OF RARE LICHEN SPECIES Lobaria pulmonaria IN RUSSIA. 10022 records from SEWBReC Amphibians (South East Wales). 2471 records from Données malacologiques des membres du Collectif GERMAIN. 9145 records from (Appendix 8) Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 3497 records from Colecção Entomológica do Departamento de Sanidade Vegetal - Ministério da Agricultura e Segurança Alimentar. 742 records from Composición y estructura de la ornitofauna de la reserva de la biósfera Pantanos de Centla. 1781 records from The Broward College Insect Collection. 76 records from Relative abundance of coccosphere-units of sediment core GIK23411-5. 1071 records from Ibaraki Nature Museum, Mammals collection. 69 records from Schulgarten mit Klasse 8a (Essen). 1964 records from Berea College, Ralph L. Thompson Herbarium. 31 records from Macrohongos de los bosques montanos del Oriente Antioqueño, Cañón del río Melcocho, en el municipio de El Carmen de Viboral, Antioquia - Proyecto Colombia BIO. 3 records from Pterophoridae (Lepidoptera) fauna of the Republic of Tuva. 27 records from Benthic foraminifera abundance of Hole 34-320A. 13624 records from Ecosphère_2017_12_18. 1 records from A new species of Leioseius (Acari: Ascidae) from Brazil, redescription of Leioseius basis and a key for separation of the world species of the genus. 3 records from Rediscovery and redescription of a deep-sea shrimp Lebbeus longidactylus (Kobjakova, 1936) (Crustacea: Decapoda: Caridea: Thoridae) based on material from the Nemuro Strait, southwestern Sea of Okhotsk. 74 records from (Table 8) Distribution of ostracode species in surface sediments of the eastern Laptev Sea. 98 records from Twite national sample survey in the UK in 1999. 77043 records from Actualización y enriquecimiento de las bases de datos del proyecto de evaluación y análisis geográfico de la diversidad faunística de Chiapas. 770 records from Isle of Wight non-native invasive species. 1489 records from Dinoflagellate cysts counts of sediment core MD95-2010. 12 records from Quill mites (Acariformes: Syringophilidae) associated with birds of Mexico. 581 records from Floristic records in the Moscow and Novgorod regions. 2 records from The sharpshooter genus Iragua Melichar: a new Colombian species, the female of I. ferruginea Cavichioli, and a key to males of the genus (Insecta: Hemiptera: Cicadellidae: Cicadellini). 5 records from A new species of Megatibicen endemic to Mescalero-Monahans shinnery sands (Hemiptera: Auchenorrhyncha: Cicadidae). 68 records from Total foraminifera counts of multinet M21/4_MSN701. 8841 records from Lothian Wildlife Information Centre Secret Garden Survey. 5 records from Sertania gen. nov., a new genus of butterflies (Lepidoptera: Riodinidae) from the South American dry diagonal. 1102 records from Plantas laguna El Tinije. 4944 records from Données Ongulés et Lagomorphes en Bretagne de 2000 à 2016. 287870 records from Florida Keys Reef Visual Census 2014. 28 records from Phytoplankton abundance at station Casma_2003-01-30_2, Casma, Peru. 430 records from Chilopoda Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 607 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 28 records from Additions to Andiorrhinus (Turedrilus) (Rhinodrilidae, Clitellata) from Eastern Amazonia. 2550 records from (Table 1) Distribution of nannofossils in DSDP Hole 87-582B. 6961 records from Collection Coleoptera SMF. 177 records from Spießwoogtal / Königsbruch (Fischbach). 7 records from Redescription of two species and five new species of Dispio Hartman, 1951 (Spionidae: Polychaeta) from the eastern Pacific Coast and Caribbean Sea, with a review of the genus. 1027 records from Inventario de Flora de la Reserva Forestal Protectora Regional de los Cañones de los Ríos Melcocho y Santo Domingo. Municipio de El Carmen de Viboral-Antioquia. 1 records from Redefinition of Denisiella Folsom & Mills, 1938 (Collembola: Sminthurididae) with description of three new species from Brazil. 565 records from Colección Zoológica Universidad del Tolima (CZUT) - Arácnidos. 184 records from Diversity, standing stock and distribution of living benthic foraminifera suborder groups (Table 3+5). 93 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Mollusca (ZUFMS-MOL). 18825 records from Análisis de las relaciones entre las diversidades alfa, beta y gamma a distintos niveles de escala espacial: Procesos históricos y ecológicos que intervienen. V Etapa. 48133 records from Records from the NIWA AllSeaBio marine biology database. 882 records from Inventario de Fauna Vertebrada de la Reserva Forestal Protectora Regional de los Cañones de los Ríos Melcocho y Santo Domingo. 95 records from Ortelsbruch - Hangmoor bei Morbach. 7239 records from Shellfish specimens of the Nishinomiya Shell Museum, Japan. 38 records from KTU Pteridophyta. 6180 records from Plecoptera. 1 records from A new species of Hippopsis Lepeletier & Audinet-Serville, 1825 from Panama and key to species (Coleoptera, Cerambycidae, Lamiinae). 1562 records from Données d'expertise convention GTM. 14 records from Contributions to the taxonomy, identification, and biogeography of Thaumatogelis Schwarz, 1995 (Hymenoptera: Ichneumonidae). 3 records from Diversity of Sternaspidae (Annelida: Terebellida) in the South China Sea, with descriptions of four new species. 80 records from Total foraminifera counts of multinet M21/4_MSN704. 156 records from Royal penguin Eudyptes schlegeli census and observations at North Head, Macquarie Island 1952/53. 1 records from Water striders (Heteroptera: Gerromorpha: Gerridae) of Romania with an update on the distribution of Gerris gibbifer and G. maculatus in southeastern Europe. 1355 records from (Table T5) Planktonic foraminifera abundance of ODP Hole 170-1043A sediments. 380 records from Artenvielfalt der Nordsee - Helgoland. 3382 records from ANTARCTIC PLANT DATABASE. 15 records from Hessen-GEO-Tag am Schlossberg von Homberg/Efze. 56430 records from North East Scotland Terrestrial Mammals 1900-2017 (excluding squirrels, wild cats and marine mammals). 52811 records from Field Museum of Natural History (Botany) Fungi Collection. 18362 records from SJRP - Herbário de São José do Rio Preto. 2 records from A new species of Campylocia Needham & Murphy, 1924 (Ephemeroptera, Euthyplociidae) from Northern Brazil. 79 records from Ibaraki Nature Museum, Amphibians and Reptiles collection. 120 records from BIRDRACE The early birds. 1098774 records from WildNet - Queensland Wildlife Data. 544 records from T. L. Hankinson Vertebrate Museum (EMU) Mammal Collection. 1221 records from RECORD Orthoptera Data. 92 records from Protozoa Abundance_Microbial Parameters. 110629 records from National Plant Monitoring Scheme - England, Scotland, Wales. 3900 records from Données naturalistes de Fabien LE NOUVEL. 21 records from City of Edinburgh Natural Heritage Service - Easter Craiglockhart Pond and Marsh Survey.. 43 records from Répartition Pelophylax (Eval 2012). 1079 records from Planktic foraminifera abundance of Hole 68-502A. 62 records from (Table 4) Principal component analysis, paleotemperatures and distribution of infaunal benthic foraminifera in Late Quaternary sediments of ODP Hole 122-760A in the southeast Indian Ocean. 2 records from Morphological and genetic evolution in eastern populations of the Macrhybopsis aestivalis complex (Cypriniformes: Cyprinidae), with the descriptions of four new species. 556 records from Sistemática y biogeografía del género Xenosaurus (Squamata: xenosauridae). 7492 records from Scarabaeoidea y colección de tipos de la colección entomológica del Centro de Estudios en Zoología, Universidad de Guadalajara. 1763 records from Herpetofauna de la región marina prioritaria Corredor Puerto Madero, Chiapas, México. 20 records from New species of the orb-weaving spider genus Chrysometa (Araneae, Tetragnathidae) from oak forests near of the Pico de Orizaba National Park (Veracruz, Mexico). 1604 records from ISM Ichthyology Collection. 38 records from Fourteen new species of Pseudisobrachium (Hymenoptera, Bethylidae) from Atlantic rain forest of Espírito Santo, Brazil.. 114115 records from ESA - Herbário da Escola Superior de Agricultura Luiz de Queiroz. 4 records from Two new species of orb-weaving spiders of the genus Larinia (Araneae, Araneidae) in meridional Brazil. 2177 records from Mayfly (Ephemeroptera) records from Britain and Ireland, via iRecord. 95 records from Kystfuruskoger i Tysnes og Fusa. 12 records from A new species of the spider genus Wirada (Araneae, Theridiidae) from Mexico, with taxonomic notes on the genus and a key to the species. 362 records from Centre d'Estudis Avançats de Blanes, Macroinvertebrados Limno. 29 records from Nomenclatural changes in the higher classification of the family Tettigometridae (Hemiptera: Fulgoroidea) with description of a new tribe and new species and a review of the Iranian tettigometrid fauna. 91 records from Diatom abundance of Hole 95-613. 31412 records from SP-Bryophyta - Maria Eneyda P. Kauffman Fidalgo. 8 records from Die Bachspezies 2008/2009. 857 records from Modelación de la distribución geográfica de las Orchidaceae del Soconusco. 31 records from Big and beautiful: the Megaxyela species (Hymenoptera, Xyelidae) of East Asia and North America. 123 records from Birdrace-SportfreundeTriller-Münster. 45140 records from SIRFF - FNE Centre-Val de Loire - Données 2016. 4559 records from Ohio State University Tetrapod Division - Amphibian Collection (OSUM). 68 records from Streuobstwiese. 116 records from (Fig. 2) Abundance of Globobulimina affinis in sediment core MD95-2040. 23 records from Abundance of benthos infauna at station GIK23042-2. 381075 records from Western Australian Museum provider for OZCAM. 13073 records from El banco de datos del Herbario HCIB en línea (Fase I): Implementación del Sistema Biótica. 690 records from Benthic foraminifera counts of sediment core GIK23352-3. 3997 records from Diversidad vegetal en un gradiente en la Sierra Madre Occidental: flora y vegetación de la Región de San Javier y Yécora, Sonora. 81 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 423 records from Mamíferos voladores y no voladores del suroccidente colombiano. 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 16759 records from Colección de Hongos del Herbario de la Universidad de La Laguna: TFC Mic. 2088069 records from Bryophyte data for Great Britain from the British Bryological Society held by BRC: Atlas 2014. 1426 records from (Table 5) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-682A, Part II. 1 records from Phasmatodea Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 38 records from Caracterizacion de Reptiles del Cerro de Chageradó, Frontino- Antioquia). 28 records from Hainbachtal bei Oelsnitz / V.. 1 records from A new high-altitude species of centipede from the Andes of Ecuador (Chilopoda, Geophilomorpha, Schendylidae). 77 records from Benthic foraminiferal assemblage (dead) in MUC SC1-K, size fraction 63-150 µm. 19 records from Small Cow-wheat distributions for Scotland 1999 to 2005. 33 records from Waldstück am Schullandheim Bad Bederkesa. 1 records from Review of Anasillomos Londt, 1983 with the description of a new species (Insecta : Diptera : Asilidae). 3 records from Two new species of Austrotinodes Schmid (Insecta, Trichoptera, Ecnomidae) from southeastern Brazil. 334 records from Aves de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 35481 records from Naturalis Biodiversity Center (NL) - Diptera. 1 records from Données naturalistes d'Olivier DELZONS. 616 records from (Table AT6) Planktonic foraminiferal stratigraphy of ODP Hole 182-1130B. 3 records from Rediscovery of a fossil dolichoderine ant lineage (Hymenoptera: Formicidae: Dolichoderinae) and a description of a new genus from South America.. 162 records from Schulhof Gymnasium Hürth Bonnstrasse. 1 records from Arachnologie ZMK. 174 records from BIRDRACE Bon(n)apartemöwen. 37 records from Canavans Ck realignment periphyton. 538 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del municipio de Pie de Pepe, Chocó. 2 records from The subfamily Cratocentrinae (Hymenoptera: Chalcididae): reappraisal of their morphological characters and review of the West Palaearctic species, with the description of two new species. 2 records from Neue Oribatiden (Acari) aus Deutschland III. Suctobelba carcharodon n. sp. und Suctobelba prominens n. sp.. 6357 records from Distribution of foraminifera of sediment core GIK23258-2. 2606 records from Range table from planktonic foraminifers in ODP Hole 157-953A. 2 records from Zooplankton abundance measured on water bottle samples during Jan Mayen cruise JM6. 196 records from Systematic revision of the Andean butterfly genus Orophila Staudinger, 1886 (Lepidoptera: Nymphalidae: Biblidinae). 20293 records from NatureShare. 1 records from A new leaf-galling Holopothrips (Thysanoptera: Phlaeothripidae) and the structural alterations on Myrcia retorta (Myrtaceae). 3 records from Two new Cyphoderus (Collembola: Paronellidae) of “ tridenticulati ” and “ bidenticulati ” groups from Brazilian Amazon. 8 records from Occurrences of Boeckella at high latitudes in the southern hemisphere. 19 records from Landesgartenschau. 22 records from Wildgehege Glauer Tal (Naturpark Nuthe-Nieplitz). 29778 records from Mycology herbarium, Tromsø Museum. 42 records from Taxonomic revision of the Cis-Andean species of Mylossoma Eigenmann & Kennedy, 1903 (Teleostei: Characiformes: Serrasalmidae). 235 records from Planktonic foraminifer occurrences and zonations from IODP Hole 313-M0029A. 393 records from Heinersdorfer Sumpfwiese. 46865 records from Mammal records from Britain from the Atlas of Mammals (1993), with some subsequent records. 136104 records from ARABEL - Arachnologia Belgica. 247 records from UCM Vertebrate Observations Collection (Arctos). 3110 records from Dead benthic foraminifera of surface sediment of the Persian Gulf (Table 2). 33416 records from Wolli Creek Preservation Society Bird Survey. 9603 records from Seabird Observations, Storm Bay, Tasmania, Australia, 1991-1994. 583 records from (Table S2) Relative abundance of coccolithophora in sapropel S1 of ODP Hole 160-964B, filtering preparation. 61268 records from MLZ Bird Collection (Arctos). 274 records from Bernhardsthal. 125 records from Naturschutzgebiet Müchelholz (Mücheln). 2 records from A new species of Phintella from Angola (Araneae: Salticidae). 7 records from Taxonomy of calcareous sponges (Porifera, Calcarea) sampled on artificial substrates of a recreational marina in the Tropical Northeastern Brazilian coast. 4 records from Two new species of freshwater, cave-dwelling crabs of the genus Neostrengeria Pretzmann, 1965, from Colombia (Crustacea: Decapoda: Pseudothelphusidae). 163 records from Wiese am Waldrand (Gurtweil). 148 records from Flora de los ecosistemas de la zona alta del río Coello (Tolima, Colombia). 6860 records from Mammal assemblages recorded by camera traps inside and outside the evacuation zone of the Fukushima Daiichi Nuclear Power Plant accident. 2829 records from (Figure 3) Stratigraphic distribution of planktonic foraminifera in the Neogene of ODP Hole 122-761B. 3962 records from Leicestershire and Rutland Aculeate Records. 177 records from Range table from benthic foraminifers in ODP Hole 174-1072A. 10110 records from Suivi Temporel des Libellules (STELI). 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Akassine*. 78 records from Museu Paraense Emílio Goeldi - Myriapoda Collection. 930 records from Herpetological (amphibian & reptile) specimens of Ryukyu University Museum (Fujukan). 50763 records from MAC - Herbário do Instituto do Meio Ambiente do Estado de Alagoas. 1194755 records from First Bird Atlas. 33 records from Taxonomic revision of the Palaearctic Tetramorium chefketi species complex (Hymenoptera: Formicidae).. 1153 records from RV Investigator Voyage IN2017_V02 Seabird Observations, Australia (2017). 72 records from Empria and Monsoma in Japan. 71 records from GPMM_Environnement_2017_12_18. 321 records from Vegetación de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 18 records from Kinorhyncha specimens of Ryukyu University Museum (Fujukan). 17 records from Reptilia ZMK. 90599 records from Ibaraki Nature Museum, Vascular Plants collection. 1 records from Redescription of the poorly known crab spider Xysticus spasskyi (Araneae: Thomisidae). 1542 records from University of Ghana - Ghana Herbarium. 5021 records from Sistematización de la colección entomológica y actualización de la colección del herbario CHIP del Instituto de Historia Natural y Ecología (IHNE), Chiapas. 8624 records from Digitization of plant specimens from Rhoen and Vogelsberg (FULD). 103 records from BIRDRACE Resopal-Darmstadt-Dieburg. 432 records from Abundance of large foraminifera in cores from transect HYD-02A, IODP Expedition 325. 381576 records from C.A. Triplehorn Insect Collection (OSUC), Ohio State University. 43 records from Revision of Brada Stimpson, 1853, and Bradabyssa Hartman, 1967 (Annelida, Flabelligeridae). 5 records from Description and molecular phylogeny of Axinella nayaritensis n. sp. (Porifera: Axinellida) from East Pacific and remarks about the polyphyly of the genus Axinella. 15 records from Regenwasserabfangsbecken (Erlenbach). 184 records from Range table from benthic foraminifers in ODP Hole 139-857C. 77 records from SNH Invertebrate Site Condition Monitoring 2015: Perchhall Loch SSSI. 7021 records from Catálogo de los equinodermos recientes de México (Fase II). 10894 records from Occurrences of the invasive plant species Heracleum sosnowskyi Manden. in the Komi Republic territory (European North-East Russia). 964 records from Arachnida del Museo de Entomología de la Universidad del Valle. 2807 records from Natura 2000 Vallée de la Seille. 591 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 2. 1025 records from Benthic foraminifera abundance of Hole 95-613. 10678 records from Inventario de Hymenóptera; parasítica en México. 2 records from Amazoniaseius imparisetosus n. sp., n. g.: an unusual new phytoseiid mite (Acari: Phytoseiidae) from the Amazon forest. 378 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 388 records from Nannofossil abundance of Hole 4-30. 8560 records from Colección de insectos agrícolas del proyecto diversidad en sistemas de cultivos. 1704 records from Données naturalistes d'Anita GEORGES. 382 records from Invasive Non-Native Species, Outer Hebrides. 18589 records from Naturalis Biodiversity Center (NL) - Crustacea. 31 records from Phytoplankton abundance at station Casma_2003-01-07_1, Casma, Peru. 113 records from Abundance of radiolaria at station UT99-13-2. 232 records from Filogenia de las cactáceas columnares (Pachycereeae) con base en caracteres anatómico-morfológicos. 10714 records from Danish Ants (Formicidae). 21 records from Brown algae specimens of Komatsu City Museum. 5686 records from Catálogo taxonómico y biogeográfico de los radiolarios (orden Polycystina) de la región central y sur del Golfo de California. 1 records from Synthèse de la Répartition des populations de bouquetin des alpes en 2010 (réseau Ongulés sauvages ONCFS-FNC-FDC). 1420 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2010. 1995 records from Monitoreo y morfometría de la avifauna de la Universidad del Valle 2011-2012. 15742 records from Insect Collection of Saitama Museum of Natural History. 6 records from Ökosysteme rund um Wedel. 737 records from Museu Valencià d′Història Natural - Fundación Entomológica Torres Sala: FETS. 29 records from Genetic variation of the 30 beech stands across three exploratories. 1 records from A new edible cricket species from Africa of the genus Scapsipedus. 13565 records from Bryophyte diversity in forests. 322 records from Triebesbach (Zeulenroda-Triebes). 76 records from BIRDRACE Nachtigallen. 1 records from List of leaf beetles (Coleoptera: Chrysomelidae) from Lagodekhi reserve with new records for Transcaucasia and Georgia. 1072 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Bryozoa. 61 records from Données de Midi-Pyrénées transmises par Pascal Peyrache.. 1286 records from ConDidact Citizen Science Surveys - Amphibians 2007. 5 records from Three new species of Leptanilloides Mann from Andean Ecuador (Formicidae: Leptanilloidinae).. 91621 records from Yorkshire Wildlife Trust - Non-sensitive records from all taxonomic groups. 4069 records from Restauración experimental de un popal invadido por el zacate alemán (Echinochloa pyramidalis, POACEAE) en el sitio Ramsar No. 1336 La Mancha y El Llano. 145 records from Abundance of radiolaria at station LV28-66-1. 49 records from Total foraminifera counts of multinet FCA97C_MSN1345. 96 records from Données naturalistes (Rhopalocères et Zygènes) de Jude LOCK (indépendant). 124 records from Biodiversidad del orden Araneae (Arachnida) de las Islas del Golfo de California, México. 1535 records from (Table 5) Distribution of planktonic foraminifera in the latest Pliocene to Holocene section of ODP Hole 149-898A. 129 records from SNH Invertebrate Site Condition Monitoring 2013/14: Glenmore Forest SSSI. 1130 records from BIOLOGICAL SCIENCES DATA. 6 records from Sandsitermes gen. nov., a new nasute termite genus from South America (Isoptera, Termitidae, Nasutitermitinae). 2936 records from Colección Botánica-Herbario. Museo de Ciencias Naturales y Antropológicas “Juan Cornelio Moyano” (Mendoza, Argentina). 96 records from Wiese und Weide am Waldrand von Gusterath. 10 records from SyNoeca ilheeNsis sp. nov., a new social wasp (Hymenoptera, Vespidae, Polistinae) from Brazilian lowland Atlantic Forest. 30 records from Phytoplankton abundance at station Sechin_2003-12-17_2, Casma, Peru. 455 records from Unna-Mühlhausen, Wiesen. 727 records from IBF Monitoring of Plant Galls. 166718 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 47 records from Distribución de la Nutria (Lontra longicaudis) en la cuenca baja del río Sinú en el departamento de Córdoba. 103 records from Birds Specimens of Akita Prefectural Museum. 3 records from Certain species of Plecoptera from the headwater springs of National Integration River (São Francisco), Brazil. 1 records from A new species in the troglomorphic scorpion genus Troglotayosicus from Colombia, representing the northernmost known record for the genus (Scorpiones, Troglotayosicidae). 19 records from Données naturalistes de LE GLOANEC Vincent. 57451 records from Calf of Man (Isle of Man) Bird Observatory Daily Logs, 1959-64, 1974-5. 370 records from Size of planktic foraminifera at CTD station PS55/051. 22424 records from MSUM Ichthyology and Herpetology Collections. 1144 records from Herpetofauna de la región El Huizache, San Luis Potosí. 36455 records from Leicestershire and Rutland Fungi and Lichen Records. 869 records from Phytoplankton abundance in surface water in January 1996, Paita, Peru. 288 records from (Appendix 6) Benthic foraminifera at termination II in sediment core GIK23256-1 in the Arctic Ocean. 369 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 4 records from Two new species of Psephenops Grouvelle (Coleoptera: Byrrhoidea: Psephenidae) from Panama. 31014 records from River Biologists' Database (EPA). 11422 records from CABI Africa Invasive and Alien Species data. 7448 records from Eurobodalla Regional Botanic Gardens. 22 records from New species of the subfamily Braconinae (Hymenoptera: Braconidae) from the Russian Far East. 1521 records from (Table T1) Nannofossil abundance of volcaniclastic and other lithologies from ODP Hole 197-1203A. 55 records from Great Eastern Ranges - Slopes to Summit. 2 records from The bees of the genus Colletes Latreille (Hymenoptera: Colletidae) of the Caucasus region. 48394 records from Tiroler Landesmuseum Ferdinandeum. 67 records from Tongrube bei Hettstedt. 95 records from Anfibios y reptiles de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 6 records from A new widespread European bee species of the genus Dasypoda Latreille (Hymenoptera, Apoidea). 1 records from A new species of the genus Comaroma in China (Araneae: Anapidae). 5 records from Evaluación de la situación de Tillandsia mauryana en el Apéndice II de la CITES, según su estado de conservación y comercio. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 8324 records from Odonata records from RSPB Reserves 1970-2009. 2 records from The first record of the genus Desertoniscus Verhoeff, 1930 (Isopoda, Oniscidea, Agnaridae) from Europe, with the description of a new species. 16098 records from The BCT/MTUK Bats & Roadside Mammals Survey. 2 records from Description of the female and egg of Phantasca phantasma (Westwood, 1859) (Phasmatodea: Diapheromeridae: Diapheromerinae). 1031 records from Données supplémentaires Atlas des Mammifères marins. 83 records from The genus Anisoscelis Latreille (Hemiptera: Heteroptera: Coreidae: Coreinae: Anisoscelini): new species, taxonomical arrangements, distributional records and key. 9 records from Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae). 1 records from Bryozoans Specimens of Akita Prefectural Museum. 130 records from Abundance of dead benthic foraminifera in sediment core CD86_02_BC5. 18 records from Anfibios presentes en el Cerro Jánano. 73190 records from CSIRO, Soviet Fishery Data, Australia, 1965-1978. 1577128 records from NBIS Records to December 2016. 149 records from Abundance of radiolaria at station UT99-23-2. 983 records from Plant specimens of Natural History Museum, Kishiwada City. 17762 records from Inventario avifaunístico de las áreas focales Zoh-Laguna y La Montaña en el corredor biológico mesoamericano Sian Ka'an- Calakmul, México. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 6 records from A new species of Metrobates Uhler, 1871 (Hemiptera: Heteroptera: Gerridae) from Colombia. 289 records from Distribución, abundancia y selección de hábitat de especies de aves amenazadas y en peligro de extinción en los bosques de montaña de Chiapas. 2439 records from Survey and monitoring records for Scottish Wildlife Trust reserves from reserve convenors and Trust volunteers - Unassessed data. 2859 records from Planktic foraminifera abundance in counts of Hole PRAD1-2. 109 records from Benthic foraminifera abundance of Hole 56-436. 7056 records from School and gummy shark tagging by CSIRO in southern Australia: 1947-1956. 889 records from Coléoptères Silphidés du département du Loiret. 17575 records from SP-Algae - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo - Coleção de Algas. 285 records from NSG Hülenbuch Hörnle (Tieringen/Meßstetten). 2267 records from Distribution of living benthic foraminifera in surface sediments of the Norwegian Sea (Table 2). 118 records from Observation des insectes sur le territoire de la Métropole Rouen Normandie. 192 records from Alterra (NL) - Microarthropods inventory in Cranendonck area. 177 records from Tejidos colectados en la caracterización biótica para la conservación de especies amenazadas en el área de influencia del Oleoducto Bicentenario, departamentos de Arauca y Casanare, Colombia. 13 records from Hazel Dormouse in Ireland. 106 records from Distribution of planktic foraminifera (125-250 µm) of box sediment core PS1246-2. 2 records from Two new species of Polana (Hemiptera: Cicadellidae: Iassinae: Gyponini) and redescription of Polana (Striapona) desela. 30 records from Nannofossil abundance in sediment core PS1313-4. 51 records from Schulteich/Tümpel Thor-Heyerdahl-Gymnasium (Kiel). 39 records from Coccoliths in sediment core GIK23059-2. 6248 records from The Fungal Collection at the Botanische Staatssammlung München. 651444 records from Phanerogamic Botanical Collections (S). 123 records from Total foraminifera counts of multinet M21/4_MSN694. 39248 records from Insects, Outer Hebrides. 11125 records from Marine Invertebrata specimen database of Osaka Museum of Natutal History. 46 records from An der Ohm, (Wettsaasen). 13024 records from Herbarium specimens of Hokkaido University Museum. 2 records from Anisops sardeus Herrich-Schaeffer, 1849: first records from Hungary (Heteroptera: Notonectidae). 1 records from A New Genus and Species of Blind Sleeper (Teleostei: Eleotridae) from Oaxaca, Mexico: First Obligate Cave Gobiiform in the Western Hemisphere. 173 records from Lichen specimens of Okinawa Prefectural Museum & Art Museum. 168 records from Restauración de flora y repoblamiento de fauna nativa en 1,000 hectáreas para el restablecimiento del corredor biológico costero en la Laguna Madre, Tamaulipas. 477 records from Anfibios y reptiles del municipio de Cuetzalan del Progreso, Puebla. 3 records from Range table from planktonic foraminifers in ODP Hole 169-1038E. 13527 records from Distribution Atlas of Butterflies in Ireland 1979 (An Foras Forbartha). 1 records from Taxonomic revision of Intybia Pascoe, 1886 species (Coleoptera, Malachiidae) of Thailand and Philippines. 969 records from Gurgltal (Tarrenz). 91 records from Radiolaria assemblage in sediment core GIK23400-3. 1 records from A New Species of Deep-channel Electric Knifefish Compsaraia (Apteronotidae, Gymnotiformes) from the Amazon River. 701 records from Range table from benthic foraminifers in ODP Hole 151-913B. 216 records from Phytoplankton abundance at stations off Punta Falsa in August 1995, Piura, Peru. 22 records from Ictiofauna Asociada a los Cativales del Municipio de Riosucio, como Aspecto Relevante dentro de la Estructura Ecológica Principal del Chocó Biogeográfico. 73 records from Rhopalocères du PNR Périgord Limousin au 15/10/2015. 1797 records from Phytoplankton abundance during Arnold Veimer cruise AV90/2. 1985 records from (Table 16) Distribution of planktonic foraminifera in the late Paleocene to earliest Oligocene section of ODP Hole 149-900A. 124 records from Kirkliston Range stream monitoring. 15 records from Australian Marsh Beetles (Coleoptera: Scirtidae). 9. The relations of Australasian Ypsiloncyphon species to their Asian congeners, additions, mainly to Petrocyphon and Prionocyphon, and a key to Australian genera of Scirtinae. 1 records from A new species of Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Caribbean Sea. 2006 records from (Table T4) Planktonic foraminiferal stratigraphy of ODP Hole 173-1069A sediments. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 345 records from UWYMV Herpetology Collection (Arctos). 11873 records from Midden-Limburg Fish Ponds Survey. 33520 records from Herbarium Senckenbergianum (FR) - Fungi. 2222 records from NU: KwaZulu-Natal Invasive Alien Species (1821-2011). 1990 records from Fish Collection of Coastal Branch of Natural History Museum and Institute, Chiba. 6 records from Review of the Eulimnadia (Branchiopoda: Spinicaudata: Limnadiidae) from Argentina with the description of a new species. 1932 records from Plant specimens of Bihoro Museum. 21 records from Mastofauna presentes en la ciénaga de Guineo, Riosucio, Chocó. 4 records from Distribution of meiobenthos in sediment core M23_123 (2) of the northeastern Atlantic (Table 1). 96 records from Redlisted beetles found in oak grove near Lake Østensjø. 825 records from (Table 4) Stratigraphic distribution of dinocyst taxa in ODP Hole 150-904A. 158 records from Planktic foraminifera counts at CTD station PS55/063. 5 records from A new species of cave dwelling Neocarus (Acari: Opilioacaridae) from Bahia state, Brazil, with remarks on taxonomic characters. 12 records from Naturschutzgebiet Swistbachaue (Eckendorf). 221 records from Museo Provincial de Ciencias Naturales “Florentino Ameghino”, Santa Fe, Argentina - Colección Squamata (no Serpentes) (MFA-ZV-Sq). 826 records from FLORA REGIONAL Y OTROS PAÍSES. MMHNSR 2018. 47 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1384. 3135 records from Hemiptera: Auchenorrhyncha: Records for Kent. 7 records from A new genus and species of owlfly from eastern and southern Africa (Neuroptera: Ascalaphidae). 25123 records from Akita Prefectural Museum, Observation Records of Birds in Akita Prefecture. 4 records from Many things come in small packages: Revision of the clawless geckos (Crenadactylus: Diplodactylidae) of Australia. 10 records from Meadow katydids (Orthoptera: Tettigoniidae: Conocephalini) from the Central-West Region of Brazil: Morphological, bioacoustic and cytogenetic study. 2 records from Hieracium attenboroughianum (Asteraceae), a new species of hawkweed. 4 records from A new remarkable and Critically Endangered species of Astyanax Baird & Girard (Characiformes: Characidae) from Chapada Diamantina, Bahia, Brazil, with a discussion on durophagy in the Characiformes. 7887 records from Inventario florístico de la región Calakmul-parte baja de la región Lacandona (Cuenca alta del Usumacinta y Marqués de Comillas). 87 records from Historical review, catalog of type specimens and online database of the ichthyology collection of the Instituto de Ciencias Naturales of the Universidad Nacional de Colombia (ICN-MHN). 32 records from ZUEC-EPH - Coleção de Ephemeroptera do Museu de Zoologia da UNICAMP. 4 records from A revision of the spider genus Raveniola (Araneae, Nemesiidae). I. Species from Western Asia. 1051 records from BOEM Beaufort Sea, Alaska, Fish and Invertebrate Haul and Catch, with Oceanography, 2008. 7 records from Mammalogie ZMK. 2565 records from Marine Turtles. 28435 records from Diversidade e ocorrência de peixes do lago Niassa (2006-2018). 659 records from An Online Database of the Immatures of Coleoptera (Arthopoda, Insecta) Described from Brazil. 4 records from Four new earthworm species of Kazimierzus Plisko, 2006 (Clitellata, Kazimierzidae). 49 records from Colección de Aráceas del Jardín Botánico San Jorge. 6010 records from Computarización de la colección de insectos de la Universidad de Morelos, CIByC, UAEM. 1 records from Erpetogomphus oxybelis sp. nov. from Veracruz, Mexico (Odonata: Gomphidae). 1048 records from Données "faune" de l'AVEN du Grand-Voyeux pour le SINP île de France. 10 records from Sediment properties of core PLG95B_06BOXG. 904 records from Thibaut_LACOMBE_2017_12_18. 3933 records from Inventario y catálogo de ostrácodos recientes de los mares mexicanos. 78830 records from Standing Waters Database - Scotland. 58 records from Abundance of living benthic foraminifera in sediment core CD86_08_BC5. 250 records from Small mammal species list 08. 3 records from Revision of the Australian Wet Tropics endemic rainbowfish genus Cairnsichthys (Atheriniformes: Melanotaeniidae), with description of a new species. 738 records from Correlación entre las condiciones ambientales y la pesquería de anchoveta a lo largo de la costa de Baja California. 2 records from Two remakable new species of Notocera Amyot and Serville, 1843 (Hemiptera, Membracidae, Hypsoprorini) from the Brazilian Caatinga. 123427 records from University of Guelph Insect Collection (DEBU). 20 records from (Table 1) Occurrences of ostracodes in ODP Hole 122-761B. 3 records from Nomenclatural changes in Mymaridae (Hymenoptera: Chalcidoidea). 48 records from Junge Heide, Radebeul/Dresden. 99 records from Naturgrundstück (Eutin). 4545 records from Stratigraphic distribution of marine palynomorph species recorded for the Miocene of ODP Hole 105-645E (Table 1). 31 records from ant-plant_symbioses. 2 records from Notes on the Agrilus fauna of the Colombian Amazon (Coleoptera, Buprestidae). 8714 records from Bird Records held by Greater Manchester Ecology Unit. 29 records from New species of Hercostomus Loew, 1857 (Dolichopodidae, Diptera) from Japan. 641 records from Colección de Zoología Invertebrados - Carcinología. 2012 records from Caracterización morfométrica del bagre rayado para la cuenca del Magdalena. 1986 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 1 records from Three new species of phytoseiid mites (Acari: Phytoseiidae) from Bahia State, Brazil. 7115 records from Records from the RHS insect reference collection. 265 records from Les mollusques terrestres de la faune de Corse : Mission 1996 de Theo RIPKEN. Muséum national d'Histoire naturelle, Paris et DIREN Corse. 69319 records from Données de l'Observatoire de la Faune de Bourgogne. 2 records from Two new eriophyoid mite species (Trombidiformes: Eriophyoidea) from the cocoa tree, and a note on Shevtchenkella biseta (Nalepa). 13 records from Five new species of Stenochrus (Schizomida: Hubbardiidae) from Oaxaca, Mexico. 3367 records from Base de datos del Municipio General Heliodoro Castillo, Guerrero (120. Sierra Madre del Sur). 677 records from Contribución al conocimiento taxonómico de los peces que habitan los sistemas acuáticos de la reserva de Calakmul, Campeche. 109 records from Host associations of Melanterius Erichson (Coleoptera: Curculionidae: Cleogonini), with a diagnosis and delimitation of the genus and description of five new species. 20 records from Données naturalistes de Jean-Patrick Le Duc. 4773 records from Museu de Ciències Naturals de Barcelona: MCNB-Tissue. 4337 records from Anillamiento de Aves Sierra Nevada de Santa Marta - Proyecto Cruzando el Caribe. 350 records from (Table 2b) Nannofossil distribution chart of ODP Hole 122-761B. 3668 records from ARKO strandeng. 322 records from Nannofossil abundance of Hole 49-408. 14 records from Colección de diatomeas del Herbario "Jaime Andrés Rodríguez". LEB-Diatomea. 368 records from Biological Recording in Scotland - Bumblebee Survey. 173511 records from Allan Herbarium (CHR). 134933 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 2 records from A new species of iguanid lizard, genus Stenocercus (Squamata, Iguania), from the Central Andes in Peru. 3979 records from Fungal Collection of Natural History Museum and Institute, Chiba. 14046 records from Actualización de la base de datos de hongos macroscópicos de Jalisco. 4 records from Two new species of freshwater crayfish of the genus Faxonius (Decapoda: Cambaridae) from the Ozark Highlands of Arkansas and Missouri. 8 records from Description of lithologic section units of IODP Hole 325-M0049B. 20 records from MVZ Herp Observations (Arctos). 245 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 5 records from First record of Psilacrum Becker 1912 (Chloropidae, Diptera) from Brazil, with the description of a new species. 18007 records from Cercle des mycologues de Montréal Fungarium (CMMF). 265 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1244-2. 497872 records from CRBPO : STOC, Baguage. 229 records from Vorderer Tiergarten (Dessau). 550 records from Naturalis Biodiversity Center (NL) - Pisces. 216915 records from Carnet B Lorraine. 18 records from Halaelurus maculosus n. sp. and H. sellus n. sp., two new species of catshark (Carcharhiniformes: Scyliorhinidae) from the Indo-West Pacific.. 5 records from Species delimitation in the Gehyra nana (Squamata: Gekkonidae) complex: cryptic and divergent morphological evolution in the Australian Monsoonal Tropics, with the description of four new species. 49 records from The genus Phlesirtes Bolivar, 1922 (Orthoptera: Tettigoniidae: Conocephalinae, Conocephalini; Karniellina), a review of the genus with data on its bioacoustics and the description of new species. 451 records from Counting of benthic foraminifera of ODP Hole 182-1132B. 5 records from Nannofossil abundance of Hole 16-157A. 315 records from Myxomycetes collection of the University of Eastern Finland. 321633 records from Seasearch Marine Surveys in England. 23 records from Black fungus gnats (Diptera: Sciaridae) found in association with cultivated plants and mushrooms in Australia, with notes on cosmopolitan pest species and biosecurity interceptions. 348 records from (Appendix 6) Benthic foraminifera at termination II in sediment core PS1906-2 in the Greenland Sea. 2313 records from PAMP-tracheo: Vascular plants in Pamplona Basin (Navarra, Spain). Undergraduate thesis, D. Vicente. 61 records from BIRDRACE Kollektiv Eisente. 27033 records from Fishes in MZNA-VERT: cyprinid and salmonid communities in the rivers Erro and Urederra (Spain). PhD project, Cristina García-Fresca. 1284 records from Mammal records captured from Licence Returns submitted to Natural Resources Wales. 2 records from A new species of sponge-dwelling Elacatinus (Pisces: Gobiidae) from the western Caribbean.. 308 records from Tejidos de la expedición en el páramo de Rabanal, Boyacá - Proyecto Boyacá BIO. 6 records from Revising the generic characters of Lobogonodes Bastelberger, 1909, with description of a new species from Taiwan (Lepidoptera: Geometridae: Larentiinae). 60103 records from DBG Kathryn Kalmbach Herbarium. 8772 records from Collection Trichoptera - SMF. 27954 records from Insect specimens of Tochigi Prefectural Museum. 160 records from Integrierte Gesamtschule Flensburg Wiemoosgraben. 896 records from SEWBReC Slime Molds (South East Wales). 115 records from Nannofossil abundance of Hole 1-3. 107 records from Bases de datos de Tanaidaceos (Crustacea: Peracarida) del Mar Caribe mexicano y Poliquetos pelágicos del Golfo de México y Mar Caribe mexicano. 207 records from (Table 5) Carbon flux, paleoproductivity, relative abundance of foraminifera on sediment core PS2138-1. 1 records from A new skipper from China: Notocrypta ariannae n. sp. (Lepidoptera, Hesperiidae). 1638 records from Inventaire des Lépidoptères Rhopalocères et Zygènes de France métropolitaine. 92938 records from Arizona State University Hasbrouck Insect Collection. 94 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2139-1. 127 records from Collection Strepsiptera SMF. 232 records from Insectos en el municipio de San Juanito, Meta - Colombia BIO. 203497 records from Vascular plant herbarium TRH, NTNU University Museum. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 3345 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 1015 records from Inventario ictiofaunístico de los humedales de Puerto Morelos, Quintana Roo. 5 records from A new genus of katydid from the Amazon Rainforest (Orthoptera: Tettigoniidae; Phaneropterinae; Steirodontini): Ninth contribution to the suprageneric organization of the Neotropical phaneropterines. 30 records from New record of the pentatomine stink bug species Caystrus orientalis Zhang and Lin (Hemiptera: Pentatomidae) from Japan. 10670 records from Records of the Australian National Botanic Gardens Seedbank. 3700 records from MGC Herbarium of University of Malaga (Spain): MGC-Algae dataset. 3383 records from Lista florística de la Costa Grande del estado de Guerrero. 1 records from New record for the deep-sea genus Tripoplax (Mollusca: Polyplacophora) in the eastern Pacific. 1 records from The dark side of pumpkin toadlet: a new species of Brachycephalus (Anura: Brachycephalidae) from Serra do Brigadeiro, southeastern Brazil. 103 records from Métropole_Nice_Côte_d'Azur_2017_12_18. 398 records from (Table 5) Range chart of benthic and planktonic foraminifera of ODP Site 127-797. 36 records from City of Edinburgh Natural Heritage Service - Large Red Damselfly Survey. 49 records from Abundance of living benthic foraminifera in sediment core CD86_06_BC5. 308 records from Naturmiljø Bergensbanen 2015 (project number 616033). 6876 records from CNMT - Herbário Centro Norte Mato Grossense. 141375 records from Données BioObs - Base pour l’Inventaire des Observations Subaquatiques de la FFESSM. 6 records from First record of the genus Ptilocerus in the Australian Region, with the description of two new species (Hemiptera: Heteroptera: Reduviidae). 220 records from Modelación de la distribución y abundancia de las subespecies de venado cola blanca en México: implicaciones de conservación y manejo. 43 records from Collection Hydrozoa - ZSM München. 45418 records from Millipede (Diplopoda) records for Britain and Ireland to 2005. 24673 records from The reptiles and amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 60 records from Nannofossil abundance in sediment core PS1294-4. 8666 records from Royal Museum of Central Africa - True Fruit Flies (Diptera, Tephritidae) of the Afrotropical Region (ENBI wp13). 477 records from Données naturalistes d'Aurélie CHEVILLON. 8322 records from NE Scotland other invertebrate records 1800-2010. 47737 records from Geneva Herbarium – General Collection (G). 152 records from (Table 7) Percent distribution of calcareous nannofossils at ODP Hole 125-786A. 259 records from Benthic foraminifera abundance of Hole 80-549A. 16 records from Caddisflies (Insecta: Trichoptera) from Santa Catarina Lachatao, Oaxaca, México: New species, new geographical records, and checklist. 1011 records from Vegetación de los remanentes de bosque andino, municipio de San Francisco (Cundinamarca). 19337 records from NCSM Vertebrate Paleontology Collection. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 790 records from Benthic foraminiferal assamblage in the >125 micron fraction of sediment core PS1906-1 (Table 9). 6284 records from Base de datos de la flora de la Reserva de la Biosfera Chamela-Cuixmala, Jalisco, México. 66 records from Characidium longum (Characiformes: Crenuchidae), a new fish from Venezuela.. 336 records from (Table T4) Biogenic and mineral composition of sediments cored in Hamburg-Langenhorn. 347 records from Orchideenstandort Nostengraben - Kretzberg (Oßmaritz). 49412 records from SPSF - Herbário Dom Bento José Pickel. 34 records from Planktic foraminifera abundance of Hole 29-279. 25 records from Myrmeleon almohadarum sp. nov., from Spain and North Africa, with description of the larva (Neuroptera Myrmeleontidae). 3 records from Lizards in pinstripes: morphological and genomic evidence for two new species of scincid lizards within Ctenotus piankai Storr and C. duricola Storr (Reptilia: Scincidae) in the Australian arid zone. 66 records from ZUEC-ECH - Coleção de Echinoidea do Museu de Zoologia da UNICAMP. 128445 records from Arizona State University Vascular Plant Herbarium. 18 records from Different continents, same species? Resolving the taxonomy of some Holarctic Ancylis Hübner (Lepidoptera: Tortricidae). 1 records from Out of the Neotropics: newly discovered relictual species sheds light on the biogeographical history of spider ants (Leptomyrmex, Dolichoderinae, Formicidae). 596 records from Colección de Herpetología de la Universidad del Quindío (HERPETOS-UQ). 88 records from Teich Berlin Wuhlheide. 186 records from Nannofossil abundance of Hole 27-259. 622769 records from Natural History Museum (London) Collection Specimens. 300 records from Ried und Sand - Artenvielfalt durch Beweidung. 20248 records from UTEP Vertebrates. 112 records from Creag Riabhach Wind Farm: 2012-13 Ornithology and Protected Mammal Surveys. 148 records from AKG-Gelände (Bensheim). 54415 records from Cawthron Institute freshwater invertebrate data. 1460 records from Range table from benthic foraminifers in ODP Hole 151-909C. 4883 records from Respaldo de las colecciones de tejidos del Museo de Zoología, Departamento de Biología Evolutiva, Facultad de Ciencias, UNAM. 348 records from Naturschutzgebiet Heiliger Hain (Wahrenholz). 3 records from Six new and one known species of Geomonhystera (Nematoda, Monhysteridae) from moss, an epiphytic plant and soil in México and Ecuador. 19 records from Distribution of planktic foraminifera of sediment core GIK23059-3 at stadium 5.5. 3 records from Revision of the genus Amytta (Orthoptera: Tettigoniidae, Meconematinae) and new species from East Africa. 133 records from Atomariine Beetle (Coleoptera) records for Britain and Ireland to 1992. 2446 records from Visual Plants (144.41.33.158) - Herbarium specimen from the Estacion Scientifica San Francisco, Southern Ecuador. 15535 records from Colección Ictiológica del Instituto Alexander von Humboldt. 128537 records from CEPEC - Herbário do Centro de Pesquisas do Cacau. 93 records from Caddisflies (Insecta: Trichoptera) from Maranhão State, Northeast Region, Brazil: A new species, checklist, and new geographical records. 80 records from Förderzentrum Schmölln. 2 records from Towards a robust systematic baseline of Neotropical fish tapeworms (Cestoda: Proteocephalidae): amended diagnoses of two genera from the redtail catfish, Phractocephalus hemioliopterus. 209 records from Lebensraum Gesamtschule (Langerwehe). 425 records from Foraminifera abundance of Hole 64-481. 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 79 records from Modelación de la distribución real y potencial de especies de dos géneros de Mimosoideae: Mimosa y Prosopis (Leguminosae) en México. 452 records from Helmintos parásitos de peces dulceacuícolas de cuencas hidrológicas del Centro-Norte de México (Durango). 87901 records from MDFRC macroinvertebrate survey. 324 records from Parc_Naturel_Régional_des_Préalpes_d'Azur_2017_12_18. 60 records from Amtsrain Apolda-Zottelstedt. 4 records from A new species of Synotaxus and the first chromosomal study on Synotaxidae, presenting a rare XY sex chromosome system in spiders (Araneae, Araneoidea). 76 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 11 records from A review of the Callogobius (Teleostei: Gobiidae) from the Red Sea with the description of a new species. 30 records from Descriptions of a new species and previously unknown males of Nesticus (Araneae: Nesticidae) from caves in Eastern North America, with comments on species rarity. 46056 records from Diversidad y dinámica del fitoplancton marino en la bahía de Acapulco, Guerrero. 143 records from Planktic foraminifera abundance of Hole 18-179. 12 records from A revision of the genus Medmassa Simon, 1887 (Araneae: Corinnidae) in the Afrotropical Region. 2 records from Calcareous sponges of the Western Indian Ocean and Red Sea. 117 records from GEO-Hauptveranstaltung Bodden (Vilm). 230 records from (Table 2) Range chart for planktonic foraminifers from ODP Hole 111-677B. 120 records from Nannofossil abundance of Hole 31-299. 3 records from Herpetology Collection. 179523 records from UF FLMNH Ichthyology. 425414 records from RECORD Vascular Plant Data. 735 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during Friedrich Heincke cruise FHE238. 227 records from Benthic meiofauna abundance in surface sediment of core PLG93_BCORE2. 1 records from Tripylella australis sp. nov. and Tripyla setifera Bütschli 1873 (Nematoda: Triplonchida: Tripylidae) from Australia. 160 records from Die Oribatiden-Arten (Acari) eines suedwestdeutschen Buchenwaldes I.. 605 records from Mollusc (non-marine) data for the Channel Islands. 78 records from Total foraminifera counts of multinet M21/4_MSN695. 390 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE206. 97 records from Dorfrand Mauderode. 3512 records from NDFF Wall Plants Monitoring Program. 7 records from Deep sea Syllidae (Annelida, Phyllodocida) from Southwestern Atlantic. 5 records from New distributional records and life stage description of Caenis species (Ephemeroptera: Caenidae) from Brazil. 28711 records from TPWD HARC Texas Coastal Fisheries Corpus Christi Bay Bag Seine. 561 records from (Table 7) Species composition of clusters, ODP Holes 139-856A and 139-857A. 181715 records from Marine benthic dataset (version 1) commissioned by UKOOA. 79 records from UNIVATES - Coleção de Ornitologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZOUMCN-UNIVATES). 11 records from A new species of Jupiaba Zanata, 1997 (Ostariophysi, Characiformes, Characidae) from the rio Tocantins drainage, Brazil.. 129 records from Total foraminifera counts of multinet POS247/2_MSN1383. 1625 records from Inventaire des Crustacés Décapodes de France métropolitaine. Données du compte CardObs 1113. 2 records from The congrid eel genus Ariosoma in Taiwan (Anguilliformes: Congridae), with description of a new species. 2209 records from Planktic foraminifera abundance in per cent of Hole PRAD1-2. 2 records from Database on reference specimens for medicinal plants of the Fabaceae family, conserved at the CNARP herbarium. 1 records from Description of the imago of Neocapritermes utiariti (Isoptera: Termitidae: Termitinae). 2 records from Taxonomic review of Athliini (Coleoptera: Scarabaeidae: Melolonthinae), a new tribe of scarab beetles endemic to South America. 931 records from Données naturalistes de Mathilde DUSACQ. 2068 records from Colecta botánica: área maya región de la Reserva Calakmul, Campeche. 1024 records from BUND - Dassower See (Lübeck/Dassow). 19 records from Description And Phylogeny Of Staminodeus, A New Genus Of Derelomini (Coleoptera: Curculionidae) Associated With Cyclanthaceae. 352 records from Birds and plant species near Petushki town (Vladimir region). 1 records from Fungal specimens of Faculty of Agriculture and Life Science, Hirosaki University. 82 records from Donación de la base de datos resultado del diagnóstico de la diversidad de maíces nativos, su agroecosistema y sus parientes silvestres presentes en Papigochic y su zona de influencia.. 984 records from Phytoplankton abundance in surface water in September 1997, Chimbote, Peru. 54298 records from Naturhistorisches Museum Mainz, Feldbeobachtungsdaten Pflanzen. 4 records from Sächsische Schweiz (Wehlener Gebiet). 134 records from Three new species, Elathous zagrosensis sp. n., Zorochros dilatatus sp. n., and Dicronychus iranicus sp. n., and noteworthy records of click beetles from western Iran (Coleoptera: Elateridae). 69319 records from Données de l'Observatoire de la Faune de Bourgogne. 2591 records from ConDidact Citizen Science Surveys - Spiders 2014. 363 records from Surface seawater carbonate chemistry, nutrients and phytoplankton community composition on a transect between North Sea and Arctic Ocean, 2008. 6067 records from Arthur Chapman Observations. 570 records from Cuxhavener Küstenheiden. 106 records from vegoek. 356 records from Dinoflagellate abundance of Hole 94-607. 1959 records from UWYMV Bird Collection (Arctos). 1587740 records from Hatikka Observation Database. 65 records from Phytoplankton abundance at station Sechin_2003-07-15_1, Casma, Peru. 62 records from Range table from planktonic foraminifers in ODP Hole 183-1139A. 36 records from Ice Algae Barents Sea. 353 records from (Table 1) Fossil record of foraminifera and ostracoda from Albersdorf clay pit, north Germany. 1 records from A new species of Masteria L. Koch, 1873 (Dipluridae: Masteriinae) from Guyana. 279 records from Banco de Germoplasma Vegetal del Jardín Botánico de Olarizu (Vitoria-Gasteiz)/Olarizuko Lorategi Botanikoaren Landare Germoplasma Bankua (Vitoria-Gasteiz). 1285625 records from PlutoF platform observations. 6 records from Two new species of Corumbataia (Hypoptopomatinae: Loricariidae) from Rio Corrente, upper Rio Paraná basin, Brazil. 4 records from Cliona acephala (Porifera: Demospongiae: Clionaida), a new encrusting excavating reef sponge from the Colombian Caribbean belonging to the Cliona viridis species complex. 4 records from The genus Spirontocaris Spence Bate, 1888 (Caridea, Decapoda, Thoridae) in western Mexico. 84 records from (Appendix B) Calcareous benthic foraminifers in ODP Hole 123-765C. 715 records from Propuesta para rescatar y conservar la paleobiota de la Cantera Tlayúa, en Tepexí de Rodríguez, Puebla: Fase II. 493 records from Pollen profile from sediment core AV14_K2-1. 11092 records from Herbario de Universidad de Murcia: MUB. 501 records from Revisión de las Agavaceae (sensu stricto), Crassulaceae y Liliaceae incluidas en el PROY-NOM-059-ECOL-2000. 2 records from A new species of Pasiphaea Savigny, 1816 (Crustacea, Decapoda, Pasiphaeidae) from the southwestern Atlantic. 1275 records from Biodiversidad de productores primarios de las lagunas costeras del norte de Yucatán. 35 records from Checklist of decapods (Crustacea) from the coast of the São Paulo state (Brazil) supported by integrative molecular and morphological data: I. Infraorder Caridea: families Hippolytidae, Lysmatidae, Ogyrididae, Processidae and Thoridae. 64 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Fósseis (ZUFMS-FOS). 798 records from El complejo Brahea-Erythea (Palmae: Coryphoideae). 20282 records from Fish specimens of Bihoro Museum. 55 records from Seeufer ehem. BUGA-Gelände. 1024 records from HBRG P.F. Entwistle Notebooks Dataset. 55 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Cragbank and Wolfehopelee SSSI. 66379 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 68 records from Kinder- und Jugendferiendorf des Kreises Groß-Gerau - Gedern/Ober-Seemen. 1 records from Description of a new Kempnyia Klapálek from Brazil (Plecoptera: Perlidae) with life stages associated using DNA barcodes. 936 records from Alterra (NL) - Microarthropods inventory in Dune vegetation. 67 records from Einen Tag lang Forscher sein - Die 5c der Erich-Kästner-Schule erforscht das Bachemer Wiesental. 65 records from Abundance of living benthic foraminifera in sediment core CD86_05_BC5. 1888 records from Benthic foraminifera and nannofossil abundance of Hole 40-360. 29 records from Brenz (Heidenheim). 232 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 1576 records from Registros Primates Neotropicales Convocatoria APC. 757 records from Arthropoda specimens of Toyama Science Museum. 4 records from Two new species of Atlantoscia Ferrara & Taiti, 1981 (Isopoda: Oniscidea: Philosciidae) from southern Brazil described in the light of integrative taxonomy. 10969 records from Records of Invasive Non Native Species held on the Cofnod database. 52 records from BIRDRACE Taubenhaucher. 2 records from Two new species of the genus Atractoscion, and resurrection of the species Atractoscion atelodus (Günther 1867) (Perciformes: Sciaenidae). 134 records from Planktic foraminifera counts at CTD station PS55/079-1. 7 records from Fiocruz/CFP - Coleção de Fungos Patogênicos. 36 records from Schulgelände Lise Meitner Realschule (Paderborn). 111 records from Birdrace-Uhulogen-Lippe. 31 records from Kurler Busch (Scharnhorst). 1 records from Description of female of Titidius urucu Esmerio & Lise, 1996 (Araneae: Thomisidae). 6882 records from La familia Asclepiadaceae en México. 369 records from BIRDRACE Havelland. 6 records from Revision of the genus Nybelinella (Teleostei, Bythitidae) with a new Atlantic, abyssal species. 7 records from DNA barcoding and morphological studies confirm the occurrence of three Atarbolana (Crustacea: Isopoda: Cirolanidae) species along the coastal zone of the Persian Gulf and Gulf of Oman. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 136 records from Birdrace-SpeedBirder-Zwickauer_Land. 366 records from Otter survey of Ireland 2004 & 2005. 17 records from Deep-water azooxanthellate Scleractinia from Vanuatu, and Wallis and Futuna Islands. 121998 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 74 records from Phytoplankton abundance measured in surface water during Charles Darwin cruise CD85. 111099 records from Suivi Temporel des Rhopalocères de France (STERF). 4 records from Description of the Nymph of Tramea binotata (Rambur, 1842) (Odonata: Libellulidae). 376 records from MalaCo, Journal de Malacologie continentale [2005-]. 23 records from Australian Museum Ichthyology - 2012 Inscription Point. 1 records from A new species of the Scinax catharinae group (Anura: Hylidae) from southeastern Brazil. 253 records from Données naturalistes d'Olivier LAURENT. 23141 records from Restauración y conservación de Isla Guadalupe. 12 records from Kindergarten. 226 records from Colección Mastozoológica Universidad de los Llanos. 26992 records from Mosses and Liverworts: Records for Kent.. 5386 records from Mollusca specimens of Wakayama Prefectural Museum of Natural History. 585 records from (Table T2) Calcareous nannofossil stratigraphy in ODP Hole 186-1151C sediments. 59335 records from USGS South Florida Fish and Invertebrate Assessment Network Crustaceans. 96 records from Warnowtal (Rostock). 13522 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 972 records from (Table 2) Distribution of benthic foraminifera on sediment core PS2138-1. 6 records from Wuhle - Brücke / B1. 48 records from SNH Invertebrate Site Condition Monitoring 2015: Tweedwood - Gateheugh SSSI. 23 records from New enigmatic species of the genus Pediobius (Hymenoptera, Eulophidae) from Afrotropics, with notes on related genera. 24910 records from Marie-Victorin Herbarium (MT) - Bryophytes. 14 records from Relative abundance of dead benthic foraminifera in the large size fraction of surface sediment off NW Africa (Table 4). 112 records from iHerbarium. 330 records from Código de barras de ejemplares de la Colección Nacional de Mamíferos del Instituto de Biología, UNAM. 23 records from Planktonic foraminifera in ODP Hole 112-688A (Table 1). 1 records from Neostasina gen. nov., a new genus of huntsman spiders from the Neotropical region (Araneae, Sparassidae, Sparianthinae). 7 records from A new species and new country records for the genus Leptobium Casey in the Palaearctic Region (Coleoptera: Staphylinidae: Paederinae). 10082 records from Données "faune" de la Société Nationale de Protection de la Nature (SNPN) pour le SINP île de France. 181 records from Dinoflagellate cysts from sediment core PS1295-4. 40 records from Abundance of benthos infauna at station GIK23013-2. 111 records from BIRDRACE Die Wendehälse. 55 records from Mauervegetation,Flechten und anderes. 281 records from Feriendorf des Kreises Groß-Gerau Ober-Seemen/Gedern. 1021 records from Phytoplankton abundance and species composition in the Gulf of Naples and the Gulf Salerno in November 1985. 180 records from New data on spiders (Aranei) from the Maritime Province, Russian Far East. 24 records from Range table from benthic foraminifers in ODP Hole 139-858D. 28 records from In situ observations of Stygiomedusa gigantea. 8332 records from Scotland Otter Survey Database. 29330 records from Buffalo Society of Natural Sciences Clinton Herbarium. 3239 records from Arthropods from Praia da Vitória (Terceira, Azores, Portugal). 8914 records from Balsfjord Nature Reserves. 1279 records from Herpetofauna de la región del Mar Muerto, Oaxaca-Chiapas. 28 records from A checklist of the Iranian Mordellidae (Coleoptera: Tenebrionoidea). 922 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC11-86. 42 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 57 records from verschiedene Kleingewässer um Oldenburg/Holstein. 206869 records from CAS Entomology (ENT). 59 records from (Fig. 2) Abundance of Uvigerina pygmaea in sediment core MD95-2040. 436 records from Platynotina (Coleoptera: Tenebrionidae) collections on the World. 23 records from Landwehrbach. 135 records from (Table S1) Relative abundances of coccolithophore taxa in surface sediment samples from the Equatorial and Southeastern Pacific. 10079 records from CSIRO, fish surveys by the Soela, 1980s. 602 records from Distribution of agglutinated foraminifers in sediment core Well 6407/7-2. 18 records from Seven new species of Loneura Navás (Insecta: Psocodea: ‘ Psocoptera’: Ptiloneuridae) from Valle del Cauca, Colombia. 2 records from A new troglobiotic Protaphorura (Collembola, Hexapoda) from the Siberia, Russia. 23622 records from Mammals Specimens. 29 records from Birkenpilz. 1339 records from Microfossil abundance of Hole 16-158. 1 records from First record of spongillaflies (Neuroptera: Sisyridae) from Colombia. 436 records from Lauri Mällo private collection of Lepidoptera. 97 records from Nematode densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 27 records from Données naturalistes de Philippe VEILLON. 50 records from Weidegut Rechab. 1136 records from CSIRO, Jack Mackerel surveys, 1978. 14904 records from Vascular Plant Specimens of Yamagata Prefectural Museum. 1106 records from Avifauna de bosques nublados en la cordillera Occidental, departamentos del Valle del Cauca, Risaralda y sur de Antioquia.. 3 records from Dichomeris Hübner, 1818 (Lepidoptera, Gelechiidae, Dichomeridinae) from Cambodia, including associated Chinese species. 2147 records from Bryophyte diversity in grassland. 896 records from Trichoptera of the UNESCO biosphere reserve of the Palatinate forest / North Vosges (Germany, France). 986 records from (Figure 3) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 103-641A. 16 records from Observations issues des suivis Argos des phoques gris en Atlantique et Manche Mer du Nord. 15 records from City of Edinburgh Natural Heritage Service - Bonaly Moorland Moth Survey. 8268 records from University Of Pretoria: Lacewing Database Project (1911-2015). 7 records from Paraorosius, a new genus of leafhopper (Hemiptera: Cicadellidae: Deltocephalinae: Opsiini), with description of a new species from the Middle East. 14 records from Perlesta armitagei n. sp. (Plecoptera: Perlidae): More cryptic diversity in darkly pigmented Perlesta from the eastern Nearctic. 507 records from Nannofossil abundance of Hole 66-490. 1307 records from Phytoplankton abundance in surface water in October 1997, Chimbote, Peru. 1 records from Synthèse de la Répartition des populations de bouquetin des alpes en 2005 (réseau Ongulés sauvages ONCFS-FNC-FDC). 23592 records from New Zealand Biodiversity Recording Network. 1462 records from Avifauna en dos parches de bosque seco del departamento del Valle Cauca (Colombia). 1 records from Données naturalistes de CARON Nicolas. 16 records from Titanogryllus n. gen., the largest Gryllinae cricket from the Neotropical Region with three new species from the Brazilian Atlantic Forest (Orthoptera, Grylloidea, Gryllidae). 2851 records from The collection of Bathynellacea specimens of MNCN (CSIC) Madrid: microscope slices and DNA extracts. 515 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 69 records from The jumping plant-lice of the Neotropical genus Tainarys (Hemiptera: Psylloidea) associated with Anacardiaceae. 50 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1018. 1530 records from Pollen analysis of sediment profile SI0 from Siethener See. 8 records from Table 1. Location, water depth, grain size distribution, organic carbon and carbonate contents of the investigated Arctic and Antarctic surface sediment samples. 1770 records from Colección Zoológica de la Universidad del Tolima (CZUT)-Anfibios. 60 records from Studies in Liocranidae (Araneae): a new afrotropical genus featuring a synapomorphy for the Cybaeodinae. 134 records from Birdrace-Team_Havelland-Havelland. 2438 records from Bird Collection of Museum and Institute of Zoology PAS. 788 records from Fauna de coleópteros lamelicornios del Estado de Michoacán. Primera Fase: Subprovincia neovolcánica tarasca (Cuenca del Lago de Pátzcuaro) 1995-96. 4 records from Review of the Oriental and Palaearctic bee fly genus Euchariomyia Bigot (Diptera: Bombyliidae: Bombyliinae). 3282 records from Sizing Ocean Giants. 28 records from New combinations, status, and species of Neotropical Ambrysini (Heteroptera: Naucoridae: Cryphocricinae). 29520 records from Inventaire et suivis d'espèces dans le Parc national des Cévennes. 173 records from Invertebrate collection of the Seto Marine Biological Laboratory, Kyoto University. 899401 records from SEWBReC Birds (South East Wales). 168 records from Die Teiche im Britzer Garten. 1 records from Laophontodes typicus T. Scott (Copepoda, Harpacticoida, Laophontodinae) - discovering a species complex by morphology. 179 records from Collection Echinodermata SMF. 48 records from Robert Forsyth Terrestrial Gastropods Collection. 237 records from (Appendix Table 3) Distribution of live benthic foraminifera in surface sediments. 455 records from Bearded Tit National Survey in Britain 2002. 782 records from Planktic foraminifera abundance of Hole 42-372. 31000 records from Elephant Seal Sightings, Macquarie Island. 313 records from Scleractinia specimens of Kuroshio Biological Research Foundation. 22484 records from Vertebrate Zoology Division - Herpetology, Yale Peabody Museum. 4492 records from Nonindigenous Aquatic Species (NAS) Database Non-freshwater Specimens. 1 records from A new species of the remarkable brittle star genus Astrophiura (Echinodermata: Ophiuroidea) from the western Atlantic Ocean. 2 records from Description of a new Gibbaranea (Araneae: Araneidae) from the Western Mediterranean. 2 records from Sammlung Ernst Ule sinenumero Herbarium Hamburgense HBG. 170 records from SNH Invertebrate Site Condition Monitoring 2013/14: Eastern Cairngorms SSSI. 302 records from Nannofossil abundance of Hole 66-488. 40 records from Heavy minerals of sediment core PL94-64. 2 records from Molecular phylogeny reveals strong biogeographic signal and two new species in a Cape Biodiversity Hotspot endemic mini-radiation, the pygmy geckos (Gekkonidae: Goggia). 132045 records from Amphibiens et Reptiles de France (Enquête 2). 3320 records from Inventario de la biota marina (cnidarios, poliquetos, moluscos, crustáceos, equinodermos y peces) del Santuario Islas e Islotes de Bahía Chamela, Jalisco, México. 1387 records from Estudio de la diversidad florística de la región de Nizanda en el Istmo de Tehuantepec, Oaxaca. 102 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1360. 97922 records from Herps Specimens. 1450 records from Données naturalistes d'Alain BERLY. 27248 records from Insect Collection from the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 813 records from Ville de Trois-Rivières - Bioblitz 2012. 2000 records from Herbarium specimens of Université de Montpellier 2, Institut de Botanique (MPU)). 22113 records from MEXU/Plantas Vasculares. 7789 records from Derbyshire Invasive Non-Native Species (INNS) 1900 - 2014. 1659 records from Inventario de macroalgas de Bahía de Banderas: Fase I y Fase II. 8613 records from University of Michigan Museum of Zoology, Division of Insects. 5148 records from Botany registration database by Danish botanists. 174 records from Colecciones Zoológicas de la Universidad de León, Colección de Gasterópodos. 4 records from Three new species of Grotea Cresson (Hymenoptera: Ichneumonidae: Labeninae) from Colombia. 1 records from Benthic foraminifera abundance of Hole 96-624. 12 records from Ohemoor (Hamburg/Norderstedt). 4 records from Redescription of Tapinesthis inermis (Araneae, Oonopidae), with detailed information on its ultrastructure. 361 records from (Appendix 4, Table 4) Relative abundances of benthic foraminifera in Late Quaternary sediments of core RC09-150 in the southeast Indian Ocean. 692 records from (Figure 1) Silicoflagellates at DSDP Hole 69-504. 13909 records from FBIP:IZIKO-UCT:Historical Invertebrates (1930-1980). 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 2723 records from Fungi specimens of Saitama Museum of Natural History. 7509 records from Collection Ichthyologie - SNSD. 826 records from Seasearch Pink Sea Fan, Eunicella verrucosa, Survey. 37 records from Naturbelassene ehemalige Wiese am Haselbach (Privates Schutzgebiet). 6704 records from Actualización de la base de datos del Herbario de la Universidad de Sonora (USON). 1116 records from Mollusca Collection of Saitama Museum of Natural History. 2 records from Taxonomy and Natural History of Strumigenys thaxteri Wheeler and Strumigenys reticeps (Kempf) (Hymenoptera: Formicidae). 36 records from BIOMEO_2017_12_18. 518 records from Fishes in MZNA-VERT: monitoring program in the Suspiro stream (Spain).. 821 records from Nannofossil abundance of Hole 29-279A. 78 records from (Table 10) Coiling ratio of Neogloboquadrina pachyderma of ODP Holes 127-794A and 127-197B. 113 records from Chough sightings data, Northern Ireland, 2007-2010. 630 records from Benthic foraminiferal assamblage in the 125-250 micron fraction of sediment core PS1906-1 (Table 6). 378 records from (Appendix A) Benthic foraminiferal abundances and principal component scores in middle to late Pliocene desiments of DSDP Hole 94-607 from the North Atlantic. 661 records from Vom Gipfel ins Moor, Transekt im NSG Allgäuer Hochalpen. 6036 records from Plantas de La Frontera (ecorregión 12.1.1.1), e inventario florístico del Rancho El Aribabi, municipio de Imuris, Sonora. 4 records from A new species of Astyanax (Characiformes: Characidae) from the endorheic Río Salí basin, Tucumán, northwestern Argentina.. 1608 records from Phytoplankton abundance in surface water in February 1998, Ilo, Peru. 163 records from Lochaber wild boar/feral pig camera trap survey, 2015. 10855 records from Fungi collection of Jyväskylä University Museum. 1185 records from Florística y biogeografía de algunos bosques mesófilos de la Huasteca Hidalguense: Fase II (Tlahuelompa y Eloxochitlán). 113 records from (Table 1) Constituents of the sand-size fraction of ODP Hole 139-856A. 4 records from Redescription of Seira pallidipes Reuter, 1895 and its synonymization with Seira pillichi Stach, 1930 (Collembola, Entomobryidae, Seirini). 120450 records from NMNH Paleobiology Specimen Records. 52 records from New records of ants (Hymenoptera: Formicidae) from Iran.. 46848 records from DMNS Bird Collection (Arctos). 2 records from Amphibian specimens of Obihiro Centennial City Museum. 1249 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany. 6107 records from Vascular Plants Specimens of Ehime Prefectural Science Museum. 1 records from Redescription and biology of Gonatopus amazonicus Olmi (Hymenoptera, Dryinidae) from Southern Brazil. 10075 records from Nematoda of Costa Rica (INBio). 83 records from Nannofossil abundance of Hole 10-89. 30284 records from Insect specimen database of Atsugi City Museum. 5 records from A checklist of seed-beetles (Coleoptera: Chrysomelidae: Bruchinae) from Iran. 82 records from DREAL_PACA_-_N2000_-_Ville_de_Fréjus_2017_12_18. 18 records from Two new species of Curculionichthys (Siluriformes: Loricariidae) from the rio Amazonas basin, Brazil. 15570 records from WTSWW Data: All Taxa (West Wales). 325 records from Fichas diagnósticas para 10 especies de anfibios y reptiles mexicanos. 412552 records from Cartografía de vegetación a escala de detalle 1:10.000 de la masa forestal de Andalucía. 192 records from "Ahrschleife bei Altenahr". 7638 records from Crustaceos del Museo de Ciencias naturales de la Universidad Simón Bolívar. 290172 records from South Australian Museum Australia provider for OZCAM. 8 records from Documenting diversity in the Amazonian butterfly genus Bia (Lepidoptera, Nymphalidae). 35 records from Urwald 3 (Bad Waldsee). 55539 records from Seasearch Marine Surveys in Ireland. 927 records from MGC Herbarium of University of Malaga (Spain): MGC-Briof dataset. 98 records from Brock University Herbarium (BU). 220 records from (Table 1) Distribution of planktonic foraminifers in ODP Hole 126-787B. 10 records from Arachnid specimens of Okinawa Prefectural Museum & Art Museum. 214 records from Distribution of planktic foraminifera (250-500 µm) of sediment core PS1246-4. 1789 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise DeHolland1986. 103702 records from Marine Commercial Fish Survey (FV Kapala, FV Trader Horn, FV Shelley, FV Kirrawa, FV May Bell) in the East and South East Australian Region from 1975 to 2008. 1003 records from (Table 2) Distribution of planktic foraminifera in early Paleogene sediments of DSDP Hole 27-259, Perth Abyssal Plain off Western Australia. 31379 records from HBRG Vertebrates (not Badger) Dataset. 29 records from An annotated taxonomic checklist of the Neotropical Gracillariidae (Lepidoptera) with links to the information on host plants and parasitoids. 3 records from Redescription of Alopecosa albostriata (Araneae: Lycosidae) based on specimens from Siberia. 6446 records from Modernisation des ZNIEFF du PnrL. 601 records from Muestreos y recolectas de flora endémica y casi-endémica de matorral costero y chaparral de la zona mediterránea Baja California, México. 207 records from Collections de coquilles continentales du Muséum d'histoire naturelle de Grenoble. 9 records from Les Rubiaceae, Orchidaceae, Moraceae, Sapindaceae, Malvaceae, Melastomataceae, Verbenaceae, Loganiaceae, Sapotaceae, Scrophulariaceae, Sterculiaceae, Liliaceae, Meliaceae, Ochnaceae, Tiliaceae, Rosaceae, Solanaceae, Violaceae, Zingiberaceae, Myrtaceae, Rutaceae, Loranthaceae et quelques 71 autres familles de plantes de l'Herbier du Centre National de Floristique en Côte d'Ivoire.. 29 records from A review of the Tillicera genus group with a revision of Plathanocera Schenkling (Coleoptera, Cleridae, Clerinae). 1059 records from irregularia_mexico. 3379 records from Highland Breeding Bird Data 2002-2003 - non-sensitive breeding species. 3 records from Cylindroniscus platoi (Isopoda: Oniscidea: Styloniscidae), a new cave-dwelling species from Lagoa Santa Karst, Southeastern Brazil. 50 records from Caracterización de la ornitofauna del Cerro Tacarcuna, Unguía, Chocó. 77 records from Australian National Insect Collection - Euryglossinae Bee Expedition 2. 616 records from (Table 15) Distribution of planktonic foraminifera in the early to early late Oligocene section of ODP Hole 149-900A. 135612 records from Tasmanian Museum and Art Gallery provider for OZCAM. 960 records from TTRS Mammals. 276 records from Mokihinui River Hydro Proposal. 3 records from Erro gen. n. a new genus of featherwing beetles (Coleoptera: Ptiliidae) from Angola and Madagascar. 67 records from Inventario Murciélagos Finca Naranjito, Aracal, Yopal, Casanare. 102 records from (Table 4b) Range chart of benthic and planktonic foraminifera of ODP Hole 127-796B. 3 records from The neotropical stingless bee genus Nannotrigona Cockerell (Hymenoptera: Apidae: Meliponini): An illustrated key, notes on the types, and designation of lectotypes. 12 records from Lepidium campestre In Häfliger & Wolf, Documenta Ciba Geigy, Dicot Weeds 1, p. 179. 1967 records from Fototrampeo de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 22853 records from Données de Lépidoptères de Denis Vandromme. 66001 records from University of Graz, Institute of Plant Sciences - Herbarium GZU. 129 records from Collection ornithologique A. Maës. 1 records from Occurrence data of Anasillomos (Diptera: Asiloidea: Asilidae). 1632 records from Determinación del estado actual de cinco especies de cactáceas amenazadas del estado de Tamaulipas, México. 2 records from Libnotes crane flies (Diptera: Limoniidae) from Jeju Island (South Korea). 5300 records from Actualización de la base de datos de diversidad taxonómica de las larvas de peces de Bahía Vizcaíno. 37 records from Mammal specimens of Komatsu City Museum. 11 records from ENS inventaires. 870 records from observe_tuna_bycatch_ecoscope. 8 records from Urban Barcode Project - Fungi. 7401 records from Natural England bat roost visit records from 2013 onwards. 270 records from ACT and Southern Tablelands Weed Spotter. 9 records from New species of Narberdia Burke from México and Central America (Coleoptera: Curculionidae). 41 records from Örtzemündung (Stedden). 3931 records from Bird specimens of Himeji City Science Museum. 64383 records from Naturalis Biodiversity Center (NL) - Aves. 1938 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 28955 records from National Stag Beetle Surveys (Great Stag Hunts). 609 records from (Appendix 8) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD99-2339. 126 records from Range table from planktonic foraminifers in ODP Hole 182-1131B. 2928798 records from Eremaea. 14 records from Benthic foraminifera abundance of Hole 96-620. 86616 records from Marine Offshore Seabed Survey data held by JNCC. 4 records from Hungarosoma bokori Verhoeff, 1928 (Diplopoda: Chordeumatida): new insights into its taxonomy, systematics, molecular genetics, biogeography and ecology. 950 records from Digitization of plant specimens from Rhoen and Vogelsberg (FLAD). 4616 records from University of Manitoba (WIN) - Lichen Collection. 1 records from Larvae of three East-Asian species of Nemoura (Plecoptera: Nemouridae). 3289 records from CSIC-Real Jardín Botánico-Colección de Hepáticas (MA-Hepat). 1 records from A new species of Enoplomischus from Kenya (Araneae: Salticidae: Leptorchestinae). 6731 records from Natural History Museum Rotterdam (NL) - Chordata collection. 166 records from Localities for the arachnid genus Acuclavella (Opiliones, Ceratolasmatidae). 2 records from Description of two new species and phylogenetic reassessment of Perelleschus O’Brien & Wibmer, 1986 (Coleoptera: Curculionidae), with a complete taxonomic concept history of Perelleschus sec. Franz & Cardona-Duque, 2013. 7 records from (Table 7) Fatty acid composition of adipose tissue from polar bears (Ursus maritimus) between 1991-2007. 569 records from Inventario de Aves Mámbita. 3085 records from NIWA Invertebrate Type Collection. 23 records from Ackerrain Plönhagen. 6844 records from Flora del Valle de Tehuacán-Cuicatlán: III fase. 146 records from Occurrence data set of Non-Timber Forest Products species for medicinal purposes in Zimbabwe’s biodiversity hotspots. 26796 records from Collections of Phytoplankton at BGBM. 43035 records from Données naturalistes de Damien AVRIL. 3 records from Freies Projekt Speichersdorf - Region Oberfranken. 1044 records from Pollen profile from Seminary School Basin. 162 records from Schulhof der Astrid-Lindgren-Schule Elmshorn. 313 records from BIRDRACE Gätkes Erben. 2 records from Replacement names for two homonyms of Liothrips brevitubus Karny: one from California, the other for a species damaging Jatropha crops in Mexico. 2012 records from Naturalis Biodiversity Center (NL) - Echinodermata. 3304 records from Benthos counted on dredged samples during Valdivia cruise VA53. 75 records from There and back again: More on the taxonomy of the crab spiders genus Epicadus (Thomisidae: Stephanopinae). 76822 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 37 records from Liether Park 2 (LMS), Klasse 6c. 4360 records from Actualización y depuración de las bases de datos de la Colección Nacional de Helmintos: P085 y Q028. 4019 records from Consolidación de la colección de referencia de peces de la Estación Mazatlán, (ICMyL-UNAM) e implementación de los mecanismos para su manejo y consulta. 102 records from Revision of Afrotropical Dyscritobaeus Perkins, 1910 (Hymenoptera: Scelionidae). 11425 records from Universitat de València, Colecciones de Criptógamas: VAL_Lich. 85 records from (Table 4) Ostracoda abundances in sediment core PS2212-3 (Yermak Plateau). 109 records from BIRDRACE Die Borner. 363 records from Noble Chafer: Post-BAP records from 1998 onwards. 689 records from RISC Non-Native Species Records for Muntjac. 966 records from Foraminifera abundance of Hole 64-481A. 4896 records from The Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 29 records from New data on the Syrphidae (Diptera) of Iran, with descriptions of two new species. 131 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V28-56. 1 records from A revision of the Neotropical ant-like genus Cardiacephala Macquart, including Plocoscelus Enderlein syn. nov. (Diptera: Micropezidae, Taeniapterinae). 20658 records from ARC-PPRI: National Collection of Nematodes and South African Plant-Parasitic Nematode Survey(1901-2014). 4 records from Taxonomic contributions to Ageniella Banks, 1912 (Hymenoptera: Pompilidae) from Brazil. 39 records from Natura 2000 Complexe de l'étang de Lindre, forêt de Romersberg et zones voisines. 2690206 records from SLU Aqua Institute of Freshwater Research National register of survey test-fishing - NORS. 26244 records from Wikiplantbase #Toscana. 16 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/312-1. 1703 records from Publicación de la obra: American species of Acacia (Leguminosae; Mimosoideae). 224 records from Bishop's University Insect Collection (BUIC). 21 records from Two new species of Brueelia Kéler, 1936 (Ischnocera, Philopteridae) parasitic on Neotropical trogons (Aves, Trogoniformes). 24 records from ALTERECO_2017_12_18. 29 records from Caracterización Ecológica de la Fauna del Páramo de Frontino o del Sol. 2401 records from Mammal collection NTNU University Museum. 42 records from Schulgarten Paul-Schneider-Schule, Münster. 70201 records from Bryophyte specimens of National Museum of Nature and Science (TNS). 310 records from Biological data from the Soviet Antarctic Expedition (1955-1958). 13 records from New species and additional data on the chewing louse genus Myrsidea (Phthiraptera: Menoponidae) from wild Neotropical Passeriformes (Aves). 25 records from Boreonemoral regnskog i Sveio. 66 records from Three new species of Anacharis Dalman, 1823 (Hymenoptera: Figitidae), with revised taxonomy and distribution records of Palaearctic and Indomalayan species. 1 records from A new species of Hemidactylus (Squamata: Gekkota: Gekkonidae) from Qara Dagh Mountains, Kurdistan Region, with a key to the genus in Iraq. 5 records from Taxonomic additions of Embolemidae and Sclerogibbidae (Hymenoptera: Chrysidoidea) from Japan, with description of a new species of Trogloembolemus. 278 records from CeDoc de Biodiversitat Vegetal: BCN- Algues de J. Rodríguez Femenías. 35 records from Nannofossil abundance in sediment core PS1293-4. 10 records from Taxonomic revision of the Neotropical genus Caenopangonia Kröber, 1930 (Diptera: Tabanidae). 9811 records from Colección, preservación y caracterización de cultivares criollos de origen español de trigo y centeno de México. 88 records from (Fig. 2) Abundance of Neogloboquadrina pachyderma sinistral in sediment core MD95-2039. 273 records from (Table 7) Benthic foraminifera genera assemblage at DSDP Section 80-548A-22. 458 records from Percentages of planktonic foraminifera species in sediment core V15-168. 134 records from Birdrace-Easy_Birders-Plön. 3 records from Taxonomy of the Capensibufo rosei group (Anura: Bufonidae) from South Africa. 9 records from A revision of the subgenus Eurycercus (Teretifrons) Frey, 1975 (Crustacea: Cladocera) in the Holarctic with description of a new species from Russian Arctic. 5375 records from (Table 1) Stratigraphic distribution of dinocyst taxa in ODP Site 150-902. 243 records from Thistles species and abundance. 61 records from Phytoplankton abundance at station Casma_2003-03-27_2, Casma, Peru. 16 records from Alpheus luiszapatai, a new species of rare and colorful deep water alpheid shrimp (Crustacea: Decapoda: Alpheidae) from Arusí, Chocó Department, Pacific Coast of Colombia. 713 records from (Appendix 4) Stable oxygen isotope record of Globigerina bulloides and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD95-2040. 8 records from Review of continental North and Central American Paracloeodes Day 1955 (Ephemeroptera: Baetidae), including description of a new species from Minnesota, U. S. A.. 38 records from Numbers and statistics of benthic foraminiferal Q-mode assemblages for the Lower Oligocene of section Poetschbichl in the Lower Inn Valley area. 500 records from The Vascular Plants Collection of the University of Goettingen. 2103 records from Flora vascular acuática de la cuenca del Río Tamesí. 797 records from (Table1) Living and dead benthic foraminifera abundance in sediments of the Bottsand-Lagoon, Western Baltic Sea. 1 records from A revision of the genus Lepidobrya Womersley (Collembola: Entomobryidae) based on morphology and sequence data of the genotype. 370 records from Distribution of ostracoda in the Arctic Ocean (Table 1). 45 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Algae. 31 records from New species and records of Perlidae (Plecoptera) from Espírito Santo State, Brazil. 2 records from A review of the North American species of the fungus-gardening ant genus Trachymyrmex (Hymenoptera: Formicidae).. 5664 records from Planktonic foraminifera, stable isotope record and temperature reconstruction of sediment core MD95-2040. 142 records from Pseudoscorpions of Ireland. 29751 records from Société_Française_d'Odonatologie_2017_12_18. 814 records from flower availability 2008 Hainich. 1854 records from (Table 2) Distribution of planktonic foraminifera in the upper Turonian-lower Campanian succession in ODP Hole 122-763B, Part III. 1 records from Two new goatfishes of the genus Upeneus (Mullidae) from Australia and Indonesia. 732 records from (Table 1) Eocene benthic foraminiferal community of DSDP Hole 95-612. 890 records from Données naturalistes de Stéphane ORIO. 3232 records from Echigo-Matsunoyama Museum of Natural Science, Usuke Shiga butterfly collection. 15 records from A new genus, four new species and taxonomic and geographic notes in Mexican Cerambycidae. 2462 records from Waarneming.nl (NL) - Great Grey Shrike Count 2011-2012. 16027 records from OUPR - Herbário "Professor José Badini". 5 records from The Oriental species of the ant genus Probolomyrmex (Insecta: Hymenoptera: Formicidae: Proceratiinae).. 1 records from On several species of Oswaldella Stechow, 1919 (Cnidaria, Hydrozoa), including the description of a new species. 234 records from (Table 6) Benthic foraminiferal genera in DSDP Core 95-612-5. 141 records from NZCS Invertebrates Old Collection Before 1987. 144 records from A taxonomic revision of the Formica rufibarbis Fabricius, 1793 group (Hymenoptera: Formicidae).. 347 records from Données naturalistes de Delphine MONTAGNE. 61 records from 20th century Betula pubescens ssp. czerepanovii tree- and forest lines in Norway. 25338 records from Global Lacustrine Diatoms. 83 records from VFD-H: Heidenrod: Pferdeweide Mürth. 56 records from Total foraminifera counts of multinet M21/4_MSN720. 7142 records from Bird collection of National Museum of Nature and Science. 12253 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 104 records from Range table from benthic foraminifers in ODP Hole 172-1059B. 426 records from Données du Centre de la mer de Biarritz. 95 records from Range table from benthic foraminifers in ODP Hole 172-1059A. 1 records from A new species of inseminating seasonal killifish of the Cynopoecilus melanotaenia complex from southern Brazil (Cyprinodontiformes: Rivulidae). 4 records from First records of Dentridactylinae (Orthoptera: Tridactylidae) from Colombia, with description of two new species of Dentridactylus Günther. 91 records from Nottekanal, Klasse 7 - 10. 595 records from Nannofossil abundance of Hole 37-333. 8 records from A new species of Hedya Hübner from Iran with proposed rearrangement of some species currently assigned to Metendothenia Diakonoff (Lepidoptera: Tortricidae). 92 records from Syndicat_Mixte_de_Défense_des_Berges_de_l'Asse_2017_12_18. 51 records from Phytoplankton abundance at station Sechin_2003-12-10_2, Casma, Peru. 4691 records from Inventaire des Mollusques Sphaeriidae de France. 709 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during LITTORINA cruise LI1986/1. 1 records from A new species of Plestiodon (Squamata: Scincidae) from the Balsas Basin, Mexico. 1 records from The identity of the Carsidara species (Hemiptera: Psylloidea: Carsidaridae) associated with Firmiana simplex (Malvaceae) in Japan and Korea. 73 records from Museo Provincial de Ciencias Naturales “Dr. Ángel Gallardo”, Rosario, Argentina - Colección Aves (MG-ZV-A). 1993 records from Inventario florístico en Baja California Sur: Región del Cabo e Islas adyacentes. 1409 records from Diatom assamblage in samples from sediment trap OG5. 255 records from (Table 3) Occurrences of ostracodes in ODP Hole 122-763B. 678 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 4072 records from Seed bank grassland. 6679 records from Données issues du dispositif de Biosurveillance des Retombées Atmosphériques Métalliques par les Mousses (BRAMM). 2 records from Redescription and designation of a neotype for Ophiothrix angulata (Say, 1825) (Echinodermata: Ophiuroidea: Ophiotrichidae). 50 records from Flora und Fauna im Brexbachtal. 299 records from (Tables 1-15) Morphometric characteristics of the genus Hinia (Nassariidae, Gastropoda) in the Tertiary of northwest Germany. 370 records from Naturalis Biodiversity Center (NL) - Micropaleontology. 199 records from Planktic foraminifera counts of sediment core RC09-150. 191 records from Herpetofauna laguna El Tinije. 91 records from Zwei Flüsse - eine Stadt (Villingen-Schwenningen). 6383 records from RSPB Reserves breeding bird surveys. 195 records from Aportación al conocimiento de la fauna de Ascidias del litoral Pacífico de México. 123 records from Birdrace-Professorenteam-Münster. 4 records from Species diversity of fiddler crabs, genus Uca Leach, 1814 (Crustacea: Ocypodidae), from Taiwan and adjacent islands, with notes on the Japanese species. 1075 records from Bryopyhtes in forest indices and traits. 6927 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos las Hermosas y Chilí-Barragán.. 5248 records from Colección de Mamíferos del Instituto de Ciencias Naturales (ICN-MHN-Ma). 332 records from Vegetación de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 2042 records from (Table 10) Distribution of planktonic foraminifers in ODP Hole 112-688A. 3887 records from Swiss National Orthoptera Databank. 1 records from Two new earthworm species (Oligochaeta: Annelida) of the Orinoquia region of Colombia. 273 records from (Table 1) Neogene benthic foraminiferal community at DSDP Hole 95-612. 30091 records from BIOWIDE eDNA Fungi dataset. 45022 records from The Environmental Sample Collection of Spiders at the Staatliches Museum für Naturkunde Karlsruhe. 1898 records from Registros biológicos Parcela permanente HATOVIAL SAS en Barbosa, Antioquia. 134 records from Pollen profile II/B at Krumbach, Germany. 60 records from Hochschule Zittau/Görlitz. 35726 records from Computarización del Herbario ENCB. Fase I (Base de datos de los ejemplares del Valle de México). 43610 records from SBC LTER Darwin Core Archive: Kelp Forest Reef Fish Abundance. 1334 records from pflanzendiversitaet_2008_sch_alb_hai_aktualisiert. 15 records from Estado actual del conocimiento biológico de algunas especies de roedores de las familias Muridae, Geomyidae, Heteromyidae y Sciuridae (Rodentia: Mammalia) incluidas en el PROY-NOM-059-ECOL-2000. 3795 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Natural Regional El Vinculo. 1 records from Multivariate discrimination and description of a new species of Tapinoma from the Western United States.. 28 records from Nationalpark Harz Schul-AG Braunlage. 1067 records from (Table T3) Planktonic foraminiferal stratigraphy of ODP Hole 173-1068A sediments. 23 records from AKG-Gelände in Bensheim. 27 records from AMF Colonization VIP 2008 Rillig. 38 records from Was lebt in der Brutzwiese?. 61 records from Phytoplankton abundance at station Sechin_2003-07-15_2, Casma, Peru. 28 records from Biodiversity Surveys, South-east Arnhem Land. 89988 records from NRW Regional Data: all taxa (excluding sensitive species), West Wales. 44 records from Planktic foraminifera abundance of Hole 19-188. 31 records from Abundance of organic-walled dinoflagellate cysts in surface sediments from the Atlantic sector of the Southern Ocean (Appendix 2). 79503 records from Michigan State University Herbarium Lichens. 49 records from Illustrated and online catalog of type specimens of freshwater fishes in the Colección de Peces Dulceacuícolas of Instituto de Investigación de Recursos Biológicos Alexander von Humboldt (IAvH-P), Colombia. 2 records from Thorectinae (Porifera: Demospongiae: Dictyoceratida) from Northeastern Brazil: two new species and transfer of Scalarispongia cincta (Boury-Esnault, 1973) to the genus Thorecta Lendenfeld, 1888. 86 records from Données naturalistes de Pierre-Alexis RAULT. 221547 records from USGS Patuxent Wildlife Research Center Seabirds Compendium. 157 records from Evaluación de la resistencia a la roya (Uromyces appendiculatus) en poblaciones silvestres y cultivadas de frijol, mediante el empleo de marcadores genéticos moleculares. 164 records from Uso y monitoreo de los recursos naturales en el Corredor Biológico Mesoamericano (áreas focales Xpujil-Zoh Laguna y Carrillo Puerto). 248 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 49 records from VFD-H.: Rheingau: Bärstadt. 3 records from Brasilisia n. gen. and Arraia n. gen., two new genera of Ocnerodrilidae (Annelida, Clitellata, Oligochaeta) from Eastern Amazonia, Brazil. 10 records from Eudraces barclayi sp. nov., with some notes on the genus Eudraces Marshall (Coleoptera: Curculionidae: Entiminae: Myorhinini). 99 records from Streuobstwiese Stedar. 20 records from Bacteria Collection of the Seto Marine Biological Laboratory, Kyoto University. 852 records from Phytoplankton abundance in surface water in November 1997, Pisco, Peru. 355 records from Relativ abundances of dead fauna of benthic foraminifera in surface sediments (Table C2.2). 78 records from Etnomicología en la Sierra de Santa Marta, Veracruz. 395 records from Pollen profile from Achenhang. 33146 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Lepidoptera_Nymphalidae_Palearctic. 183 records from Distribution of living benthic foraminifera in sediment cores of cruise M77 Leg 1 and 2, 63-2000 µm fraction. 5701 records from Gillnet test fishing and radiocaesium (Cs-137) of brown trout (Salmo trutta) and Arctic char (Salvelinus aplinus) 2008 and 2009 from 20 Central Scandinavian lakes: Occurrences. 163 records from HSU Vertebrate Museum Birds Collection. 28 records from New species of ant-mimicking jumping spiders of the genus Myrmarachne MacLeay, 1839 (Araneae: Salticidae) from north Queensland, Australia. 12 records from Kinderwald Hannover. 40 records from Coleção de Nematoda do Museu Nacional - UFRJ. 14500 records from Lepidoptera (Rhopalocera y Heterocera) de áreas prioritarias para la conservación en la Península de Yucatán, con registros de adultos y estados inmaduros. 1089 records from Foraminifera abundance of Hole 64-478. 338 records from Unser Schulgelände. 551 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Senckenberg_04_1986. 142 records from Birdrace-Alte_Socken-Cuxhaven. 9939 records from Andes to Amazon Biodiversity Program. 16 records from Collection Echinodermata - ZMB. 20 records from Two new species of Pamphobeteus Pocock 1901 (Araneae: Mygalomorphae: Theraphosidae) from Brazil, with a new type of stridulatory organ. 243 records from WildesMoor bei Schwabstedt. 362 records from Inventario herpetofaunístico del noroeste de Hidalgo. 3 records from Three new species of jumping spiders of the genus Hypaeus Simon, 1900 from Colombia (Salticidae: Salticinae: Amycini). 2 records from Description of lithologic section units of IODP Hole 325-M0052A. 9366 records from ZooplanktonBeaufortSeaNOGAP2. 1 records from Revision of the genus Hormoserphus Townes, 1981 (Hymenoptera: Proctotrupidae), with description of Trachyserphus gen. n. and a new species. 3118 records from Polychaetes in surface sediments off Sylt collected during HEINCKE cruise HE258. 511 records from Plantas del municipio El Carmen de Chucurí, Santander - Proyecto Santander BIO. 268 records from Briófitos del cerro Tacarcuna-Chocó, en el marco del proyecto Colombia BIO 2017. 37422 records from Repatriación de datos de los lepidópteros depositados en la Colección del McGuire Center for Lepidoptera and Biodiversity, Florida Museum of Natural History. 1386 records from Aves de fragmentos de Bosque seco en la región del Caribe Colombiano. 1 records from Studies on Dendrothripinae (Thysanoptera, Thripidae) from Japan, with new records and one new species. 2225 records from Jardín Botánico Atlántico, Gijón: JBAG. 950 records from Aves Collection of Institute of Systematics and Evolution of Animals. 1419 records from Diversity of algae in wetlands. 1 records from Données naturalistes de Marcel CRUVEILLIER. 4149 records from Universidad Autónoma de Madrid, Biología, Acalypha. 366 records from Weinberg Reichersdorf. 2142 records from Herbarium specimens of CBNA (GAP). 751 records from Range table from planktonic foraminifers in ODP Hole 157-954A. 6132 records from Natural history museum data on Canadian Arctic marine benthos. 559 records from DREAL_PACA_-_N2000_-_GIP_Calanques_2017_12_18. 562 records from Range table from benthic foraminifers in ODP Hole 189-1169A. 7 records from Three new species of Epigomphus (Odonata: Gomphidae) from Costa Rica. 10 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Taynish Woods SSSI. 1225 records from (Table T5) Benthic foraminifer occurrence in ODP Hole 183-1139A sediments. 3 records from Abundance of zooplankton in the Aral Sea. 11 records from Données de Lépidoptères de Bruno DAUGET - Dépt du LOIR-ET-CHER (41). 349 records from Pollen analysis of sediment profile NI0 from Niklassee. 144414 records from CONN. 2459 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 8546 records from ISM Mammalogy Collection. 85316 records from The avian collection at the Natural History Museum, Oslo, Norway. 609 records from Phytoplankton abundance in surface water during cruise CD61. 130 records from (Table 15) Distribution of ostracode species in Core PS51/135-4. 6603 records from Nijmegen Natural History Museum (NL) - Herbarium. 144 records from (Table 1) Benthic foraminiferal distribution at ODP Site 127-794. 2030143 records from Suffolk Biodiversity Information Service (SBIS) Dataset. 2335 records from Données du programme 50000 observations pour la forêt. 37 records from Nothocasis rosariae sp. n., a new sylvicolous, montane species from southern Europe (Lepidoptera: Geometridae, Larentiinae). 1170 records from Département_du_Var_2017_12_18. 127 records from Wildlife Observations Bardon Hill 31.5.09. 31 records from Projekt Wahner Heide. 1200 records from ACCDC: Rare Species in Atlantic Canada and Adjacent Marine Waters. 153 records from (Table 1) Abundance of the main species of benthic Foraminifera in the assemblage Cribrostomoides subglobosus-Tritaxis nana of the Kara Sea. 5 records from Planktic foraminifera counts of multinet M21/4_MSN724. 88511 records from University of Alberta Vascular Plant Herbarium (ALTA-VP). 196 records from Inventaire malacologique du site Natura 2000 FR9301547 du Grand Coyer (2007, ONF/MNHN). 4 records from (Table 2) Dissolution index (XDX) values and average test mass for four species of planktonic foraminifera. 50 records from Collection Arachnida - ZSRO. 344 records from Woodland Survey. 310 records from Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert sowie Umland. 10270 records from HBRG Other Invertebrates Dataset. 27 records from Two new genera and five new species of Mugadina - like small grass cicadas (Hemiptera: Cicadidae: Cicadettini) from Central and Eastern Australia: comparative morphology, songs, behaviour and distributions. 7 records from Review of the genus Cyrtosia Perris (Diptera: Mythicomyiidae: Platypyginae) in Iran, with description of three new species. 54 records from New records of Gerromorpha and Nepomorpha (Insecta: Hemiptera: Heteroptera) from South America. 51 records from Review of the Nearctic genus Scyletria Bishop & Crosby (Araneae, Linyphiidae), with a transfer of S. jona to Mermessus O. Pickard-Cambridge. 21663 records from Monitoring data from the federal state Saxony-Anhalt (Germany). 115776 records from Hymenoptera specimen database of Kyushu University. 3351 records from Macroinvertebrados y perifiton pertenecientes a cuatro regiones de Colombia. 14 records from A new western Canadian record of Epeoloides pilosulus (Cresson), with discussion of ecological associations, distribution and conservation status in Canada. 343 records from Distribution of planktic foraminifera (250-500 µm) of sediment core GIK23059-3. 651653 records from Finnish Floristic Database (Literature Sources). 4620 records from SEWBReC Algae and allied species (South East Wales). 111 records from The Myriapoda Collection of the National Museum of Nature and Science. 541 records from (Table T6) Biostratigraphy of important benthic foraminifer taxa in sediments cored in Ratekau, Schleswig-Holstein. 68875 records from Belgian Coccinellidae - Ladybird beetles in Belgium. 1773 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 1211 records from CSIRO, Cruise SS199101, Marine Biology Data, Western Australia, 1991. 633 records from Records of otters from Site Condition Monitoring in Scotland 2011-2012. 3 records from Edwardsya, a new genus of jumping spiders from South America (Araneae: Salticidae: Freyina). 6117336 records from iNaturalist Research-grade Observations. 14 records from First record of the genera Centistoides van Achterberg and Pygostolus Haliday (Hymenoptera: Braconidae) in Brazil, with the description of new species. 8928 records from City of Amsterdam (NL) - Fyke Fishing Piet Ruiter. 65 records from Cuxhaven Schlosspark, Klasse 5e- Amandus-Abendroth-Gymnasium. 11571 records from (Table 5) Stratigraphic distribution of calcareous nannofossil taxa in ODP Hole 149-898A. 6541 records from Likona Invertebrates. 2262 records from Larval fish at time series station Helgoland Roads, North Sea, in 2005. 7 records from Foraminifera study in the Horten inner harbor area. 121308 records from Dorset Sites of Nature Conservation Interest (SNCI) species records pre 2000. 334 records from Assemblage of living benthic foraminifera in sediment core GeoB3712-1. 208 records from Amphibiens de Guyane. 8 records from Distribution of meiobenthos in sediment core M23_199 (2) of the northeastern Atlantic (Table 1). 15 records from Three new species of Onychiuridae Lubbock, 1871 (Collembola, Poduromorpha) from Iran. 16572 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 9 records from Revalidation of Pterinopelma Pocock 1901 with description of a new species and the female of Pterinopelma vitiosum (Keyserling 1891) (Araneae: Theraphosidae: Theraphosinae). 16 records from Planktic foraminifera abundance of Hole 19-184. 5 records from Collection Myriapoda - SNSD. 38 records from BB-Biodiversität a. 6720 records from DBRC Hemiptera species records 1969 to 2015. 185 records from (Table 8) Relative abundance of benthic foraminifera in ODP Hole 112-682A, Part I. 1857 records from Censo de aves acuáticas nidificantes de la Comunidad Autónoma del País Vasco. 52668 records from Stackpole National Nature Reserve Species Inventory and Ad-hoc Sightings from Across Pembrokeshire. 20 records from Riedkanal Bötzingen. 39 records from Nannofossil abundance of Hole 37-333A. 27 records from Planktic foraminifera abundance of Hole 27-259. 543 records from Brood cell No. of trap-nesting species Alb 2008. 19 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 2423 records from SSNATV_2017_12_18. 20 records from Planktic foraminifera abundance of Hole 19-185. 945404 records from Dragonfly records from the British Dragonfly Society's Dragonfly Recording Network for the period up to 2014. 17769 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) planctónicas más frecuentes en el Golfo de California. 2154 records from DBG Physaria bellii Demographic Monitoring. 95 records from Überschwemmungsgebiet der Wied. 467 records from Données naturalistes (Rhopalocères et Zygènes) de Benoit DUHAZÉ (CEN Aquitaine). 5 records from A revision of the genus Disparalona (Cladocera, Chydorinae) in South America. 413 records from Phytoplankton abundance during Lev Titov cruise LT91. 61 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunción, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes. 19 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 4581 records from Códigos de barras de la vida en peces y zooplancton de México. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 62308 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 42 records from (Table 2) Major nannofossil abundances in three Leg 194 site survey gravity cores. 89 records from Birdrace-Team_Wangerooge-Friesland. 88200 records from Canadian Museum of Nature Bird Collection. 11 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/313-1. 497 records from Especies de Leptohyphes (Insecta: Ephemeroptera: Leptohyphidae) del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 2 records from Two new Afrotropical genera of Scatopsidae (Diptera). 4499 records from Moluscos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRM-UV). 45 records from Total foraminifera counts of multinet M21/4_MSN719. 584 records from Mammalia fossil Kleinsäuger - SMF. 3 records from A new species of Zethus Fabricius (Hymenoptera, Vespidae, Zethinae) from Northeast Brazil, with notes on morphology and distributional records of Z. alessandroi Lopes. 1704 records from DREAL Auvergne - Insectes - 2015. 380 records from (Table 3d) Foraminiferal distribution chart of petroleum well Great-Eastern-1. 26185 records from Données de Mammifères enregistrées dans BazNat - Lot 1. 51 records from University of Amsterdam (NL) - Páramo Vegetation Research, Bordoncillo - Nariño, Colombia. 1451 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 1 records from Gaidropsarus mauli a new species of three-bearded rockling (Gadiformes, Gadidae) from the Lucky Strike hydrothermal vent field (Mid-Atlantic Ridge) and the Biscay Slope (Northeastern Atlantic). 82 records from Range table from planktonic foraminifers in ODP Hole 169-1038I. 359 records from Pöhlberg bei Annaberg. 1924 records from Caracterización de la vegetación en una zona delimitada en Cumbitara, La Llanada, Policarpa y Los Andes Sotomayor (Nariño), como insumo para la identificación de oportunidades de conservación para la recuperación de los servicios ecosistémicos de bosque seco. 7 records from Plasm bearing foraminifera counts of multinet POS231/3_MSN1336. 64 records from "Wildnis erleben" - "Vielfalt erlebbar machen" - Botanischer Garten u.Chrimmitschauer Wald. 665 records from Planktic foraminifera counts of sediment core V04-8. 132 records from (Table 9) Dinoflagellate cyst species distribution in ODP Hole 112-684B. 104 records from Birdrace-RMD_Die_Gipfelstürmer-Main-Taunus-Kreis. 5 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 88894 records from Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 11 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Glen Tarff SSSI. 12 records from Range table from planktonic foraminifers in ODP Hole 151-912A. 4227 records from Données naturalistes de Loïc SALAUN. 1139 records from SWECO. 373 records from Dinocyst occurrences and zonations from IODP Hole 313-M0029A. 2321 records from Dataset of fungus gnats (Diptera,Sciaroidea) from Møre og Romsdal county in Norway. 59620 records from EAC - Herbário Prisco Bezerra. 1255 records from (Table 6) Planktonic foraminifera in ODP Holes 139-856A and 139-857A. 2506 records from East Ayrshire Species Database. 1200 records from Phytoplankton abundance in surface water in June 1997, Callao, Peru. 17669 records from DBG Sam Mitchel Herbarium of Fungi. 1 records from Description of a new neotropical species of Xiqilliba Kramer (Hemiptera: Cicadellidae: Neocoelidiinae). 1981 records from Collection Crustacea - ZMB. 1136 records from (Table 1) Distribution of agglutinated benthic foraminifera in lower Cretaceous sediments of DSDP Hole 27-263 in the Cuvier Abysaal Plaine, Indian Ocean. 504 records from CMC Cincinnati Museum Center Invertebrate Paleontology. 639 records from Estudio herpetofaunístico de la Sierra Mazateca, Oaxaca, México. 3349 records from Satellite tracking of female olive ridley sea turtles (Lepidochelys olivacea) nesting in the Wessel Islands, Northern Territory, 2005. 993 records from Estudio taxonómico del género Quercus (Fagaceae) en el Estado de México. 19 records from Cordulegaster virginiae sp. nov. from Mexico, including a comparison with C. diadema Selys, 1868, and a redescription of its larva (Odonata: Cordulegastridae). 1 records from A new species of Notosacantha Chevrolat (Coleoptera: Chrysomelidae: Cassidinae) from Timor-Leste with a key to the Notosacantha vicaria - group. 186 records from Abundanz_Infloreszenzenschlupf_Pflanzenebene_2008. 288 records from RHS Fuchsia Gall Mite (Aculops fuchsiae) monitoring. 827 records from Schatzinsel Norderney. 43 records from Nannofossil abundance of Hole 25-249. 1 records from Myriopoden von Epirus. 8615 records from CSIRO, Tropical Zooplankton Biomass and Composition, Albatross Bay - Gulf of Carpentaria, North Australia 1986-1988. 1352 records from ¿Existen especies de macroalgas o pastos marinos dentro del Golfo de California, que deban de estar consideradas dentro de la NOM (PROY-NOM-059-ECOL-2000)?. 228 records from Assemblage of dinoflagellate cysts analysed in surface sediment samples off Peru. 1 records from A new genus and species of Ingolfiellidae (Crustacea, Ingolfiellida) from the hyporheic zone in the Sierra de la Ventana, and its biogeographic relevance. 26 records from Four new species and one new subspecies of Arctiinae (Lepidoptera: Erebidae) from the Tambopata river, Madre de Dios, Peru. 24 records from SNH Invertebrate Site Condition Monitoring 2013/14: Dollar Glen SSSI. 11652 records from MVZ Egg and Nest Collection (Arctos). 45872 records from The national database for marine data (MADS). 204 records from Foraminifera abundance of Hole 57-440A. 19 records from Description of lithologic section units of IODP Hole 325-M0035A. 990 records from Herbario HUAZ Enrique Forero. 2 records from Coendutermes tucum Fontes (Isoptera, Termitidae, Nasutitermitinae): description of the imago caste and additional notes. 900 records from North Atlantic (Rockall Plateau) coccolith assemblage data for MIS 5 of ODP Hole 162-980B. 62 records from Kabelskebach (Kabelsketal, Saalkreis). 2 records from Four new generic and 14 new specific synonymies in Pholcidae, and transfer of Pholcoides Roewer to Filistatidae (Araneae). 110 records from Pollen analysis of sediment core GeoB1007-4. 668 records from Freshwater Macrophyte Survey Data. 5 records from Naturalis Biodiversity Center (NL) - Orthopteroidea. 447 records from Gelände des IVL (Zeckern). 48 records from Fauna herpetológica de los Parques Ecológicos Distritales Humedales Bogotá, D.C.. 634258 records from Hawk Migration Association of North America - HawkCount. 13 records from Warnowufer Groß Klein. 153 records from Planktic foraminifera abundance of Hole 18-181. 220 records from (Table 4) Distribution of calcareous nannofossils at ODP Hole 125-785A. 87662 records from E. C. Smith Herbarium (ACAD). 20192 records from Sistemática e historia natural de algunos anfibios y reptiles de México. 11335 records from Diversidad de ocho grupos de insecta (Odonata, Lycidae, Phengodidae, Lampyridae, Cantharidae, Cerambycidae, Syrphidae y Vespidae) en tres regiones con bosque tropical caducifolio en México. 12 records from Planktic foraminifera abundance of Hole 42-372. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 69 records from Museu Paraense Emílio Goeldi - Platyhelminthes Collection. 178 records from Evaluación del ámbito hogareño y calidad de hábitat del borrego cimarrón (Ovis canadensis mexicana), Berrendo sonorense (Antilocarpa americana sonoriensis) y del Puma (Felis concolor) en la Reserva de la Biósfera El Pinacate y Gran Desierto de Altar. 1004 records from Dead benthic foraminifera of surface sediments from the East Atlantic continental margin off Portugal (Table 5 & 7). 46 records from Base de datos de Rana catesbeiana.. 996 records from Phytoplankton abundance in surface water in July-August 1996, Pisco, Peru. 28 records from Uroptychus nitidus (A. Milne-Edwards, 1880) and related species (Crustacea: Decapoda: Anomura: Chirostylidae) from the western Atlantic. 1850 records from Données diverses du PnrL. 1747 records from Consolidación y sistematización de las colecciones de referencia de peces y mamíferos marinos del ITESM Campus Guaymas. 48 records from SYMBIOSE_2017_12_18. 2363 records from Avifauna en un área perturbada del bosque andino en el Parque Nacional Natural Farallones de Cali, corregimiento de Pance, Valle del Cauca (Colombia). 909 records from Caracterización del hábitat y patrones de distribución del gorrión serrano (Xenospiza baileyi) en el sur del Valle de México. 1 records from The bees (Hymenoptera: Apoidea) of the Maltese Islands. 3 records from Gynacantha dryadula sp. nov. from the Guiana Shield (Odonata, Anisoptera: Aeshnidae). 33 records from (Table 3) Sr-Nd-Pb isotope ratios of selected Cocos Plate samples. 1819 records from Inventario florístico de la Sierra de San Carlos, Tamaulipas. 136 records from Abundance of planktic foraminifera at CTD station PS55/080-1. 10 records from Description of the larval stages of the Shield Darter, Percina peltata (Pisces: Percidae), in New York.. 384 records from "Schwarzwassertal" bei Pobershau. 1932 records from (Table 5) Distribution of planktonic and selected benthic foraminifers from DSDP Hole 87-583D. 604361 records from Museums Victoria provider for OZCAM. 20187 records from Alterra (NL) - Entomofauna inventory in riverside grasslands. 26635 records from Plan de vertebrados de la Patagonia. 2400 records from Springtales from lichen communities at Kollåsen in Norway. 879 records from Herbivorie_Pflanzenebene_2008. 2 records from A new amphibious troglobitic styloniscid from Brazil (Isopoda, Oniscidea, Synocheta). 2 records from A new species of the stenopodidean shrimp genus Odontozona Holthuis, 1946 (Crustacea: Decapoda: Stenopodidea: Stenopodidae) from the Ryukyu Islands, Indo-West Pacific. 303268 records from Données acquises dans le cadre de l'activité du bureau d'étude BIOTOPE (1994 - 2013). 132 records from Range table from planktonic foraminifers in ODP Hole 167-1011C. 971 records from Danielsberg (Mölltal, Kärnten). 16988 records from LPO_PACA_2017_12_18. 95 records from Vegetación vascular terrestre, entomofauna y macrofauna de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 343 records from Sphaeriid clams. 274 records from Updated list of bumblebees (Hymenoptera: Apidae) from the Spanish Pyrenees with notes on their decline and conservation status. 222 records from Living Prairie Museum Manitoba Herbarium (LPMMBH). 588350 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 20388352 records from INPN - Données flore des CBN agrégées par la FCBN. 2845 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 1896 records from NRW Regional Data: all taxa (sensitive species only), West Wales. 439 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel. 15 records from A new species of Mesovelia (Heteroptera: Gerromorpha: Mesoveliidae) from South America, with identification key and notes on Colombian species. 6579 records from Computarización de la Colección de mamíferos del Centro de Investigaciones Biológicas del Noroeste SC. 4 records from New records of Panchaetothripinae from Japan (Thysanoptera, Thripidae). 170 records from (Table 4) Benthic foraminifera genera assemblage at DSDP Section 80-548A-11-3. 76 records from SNH Invertebrate Site Condition Monitoring 2015: Lurgie Loch SSSI. 1238 records from Diversidad y conservación de orquídeas de la región de Chimalapa, Oaxaca, México. 959 records from GBIF: Nova Scotia Museum of Natural History - Freshwater mussels. 38 records from Taxonomic revision of the Afrotropical species of Pachyanthidium Friese (Hymenoptera: Megachilidae: Anthidiini). 1857 records from TWIC Hedgehog Public Survey. 935 records from Assemblage of planktonic foraminifera for the last glacial maximum (LGM) in sediment cores from the South Atlantic. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 191 records from Lindau im Bodensee. 210133 records from Estonian Nature Observations Database. 1057 records from Hongos ectomicorrizógenos y myxomycetes asociados con Picea chihuahuana en la Sierra Tarahumara. 43709 records from Botanical Museum, Copenhagen, Mycology Herbarium. 19 records from KTU Pinophyta. 1122 records from (Table 6) Distribution of planktonic foraminifers in ODP Site 112-684. 15946 records from NCSM Mammals Collection. 40 records from Données de Rhône-Alpes transmises par Pascal Peyrache.. 34 records from Taxonomic review of Epicadinus Simon, 1895 (Araneae: Thomisidae). 328 records from Crustacés Branchiopodes Phyllopodes de France. 90 records from GEO-Tag mit der NAJU des Landkreises Ahrweiler am Bausenberg. 6 records from Studies on the genus Aeolothrips (Thysanoptera: Aeolothripidae) in Iran, with a key to species. 5 records from Fledermäuse u. nachtaktive Insekten. 7721 records from Chondrichthyans Of Ireland. 359 records from Inventaire malacologique du site Natura 2000 FR9301537 de la Montagne de Lure (2002, ONF/MNHN). 845 records from Phytoplankton abundance during HYDROMET cruise Hydromet90/4. 75383 records from Colección de Entomología del Instituto Alexander von Humboldt. 273 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto1-10. 89 records from Taxonomic note on the oil-collecting bee Centris dimidiata (Olivier, 1789) (Hymenoptera: Apidae: Centridini). 1 records from The subspecific structure of Dorcadion (Cribridorcadion) pusillum Küster (Coleoptera: Cerambycidae) with description of two new subspecies from Romania. 163936 records from Species data for Scottish waters held and managed by Scottish Natural Heritage, derived from benthic surveys 1993 to 2014. 7847 records from Insect specimens of Toyota City Nature Sanctuary. 1174 records from Sudeniederung (Amt Neuhaus). 2318 records from DREAL_PACA_-_N2000_-_Syndicat_Mixte_d'Aménagement_de_la_Vallée_de_la_Durance_2017_12_18. 134924 records from Bryophyte data for Great Britain and Ireland from the British Bryological Society held by BRC: data compiled post-Atlas. 666 records from O Tu Wharekai algae survey. 18 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2445-2. 4207 records from CASES2003_2004. 6 records from Taxonomy and biology of Simulium clarkei Stone & Snoddy (Diptera: Simuliidae), a poorly known black fly of the southeastern United States. 120 records from North Marine Region whaler shark collection records (DEW collation), Australia (1999- 2005). 349 records from Digitalización y sistematización de las colecciones biológicas del INECOL. 570 records from Flora ficológica marina de Tamaulipas. 36489 records from Fife Nature Records Centre combined dataset. 159 records from Stable isotope analysis on sediment core PS2644-2. 151 records from CHAS Botany Collection (Arctos). 34983 records from Vascular plants collection of Hiratsuka City Museum. 23 records from Description of two new species of Avicularia Lamarck 1818 and redescription of Avicularia diversipes (C. L. Koch 1842) (Araneae, Theraphosidae, Aviculariinae) - three possibly threatened Brazilian species. 3006 records from Plantas de la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 6 records from New records of species of the Polyonyx sinensis group (Crustacea: Decapoda: Anomura: Porcellanidae) from Japan, the Philippines, Singapore, and Malaysia, with descriptions of two new species. 3019 records from Colección Viva del Jardín Botánico de Bogotá. 384 records from Mammal specimens of Kawasaki Municipal Science Museum. 11 records from A new genus of nesticid spiders from western European Peninsulas (Araneae, Nesticidae). 3 records from Refining the genus Rochinia A. Milne-Edwards, 1875: reinstatement of Scyramathia A. Milne-Edwards, 1880 and Anamathia Smith, 1885, and a new genus for Amathia crassa A. Milne-Edwards, 1879, with notes on its ontogeny (Crustacea: Brachyura: Epialtidae). 821 records from Dragonfly biodiversity 90 years ago in an Alpine region: The Odonata historical collection of the MUSE (Trento, Italy). 117 records from Naturschutzgebiet Lochbusch-Königswiesen. 50 records from Microorganismos asociados con la filósfera de plantas de Espeletia en el PNN los Nevados. 53 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 1441 records from Données naturalistes de Philippe GOURDAIN (ANVL). 270 records from BIRDRACE Niederlausitz-Team. 6751 records from Odonata de Veracruz. 1464 records from Planktic foraminifera abundance of Hole 18-173. 2 records from Planktic foraminifera abundance of Hole 54-421. 21135 records from SIRFF - FNE Centre-Val de Loire - Données 2015. 279 records from Vocalizaciones de aves mexicanas en análisis biogeográficos y reconstrucción filogenética. 441 records from Línea base del medio biótico en los bosques dentro de la zona propuesta para Acuerdos de Conservación Voluntaria en la microcuenca de la Quebrada Aguazula - Rincón del Soldado_Yopal. 52 records from The water striders (Hemiptera: Heteroptera: Gerridae) of Costa Rica: new species, checklist, and new records. 642 records from British Antarctic (Terra Nova) Expedition, 1910-1913. 2643 records from UFRN-Fungos - Herbário UFRN - Fungos. 106273 records from Colección Herbario Federico Medem Bogotá - FMB. 82 records from New records of snail-killing flies (diptera: Sciomyzidae) from Iran. 226 records from SNH Invertebrate Site Condition Monitoring 2013/14: River Spey - Insh Marshes SSSI. 153 records from Shannon Index and species richness for herbivores. 217 records from 5.Tag der Artenvielfalt: Thema Stadtbiotope. 2 records from Miriapodi cavernicoli del Marocco, della Sardegna e del Piemonte. 4210 records from Actualización de las bases de datos de colecciones, especies en peligro de extinción, colecta y propagación de germoplasma. 1422 records from Reconocimiento de la biodiversidad de la Reserva de la Biósfera Calakmul: Odonata, psocóptera y díptera acuáticos (Insecta). 77 records from GenLink - Genetic diversity of Trifolium repens. 635 records from CG04_2017_12_18. 280 records from Faberpark (Nürnberg/Stein). 406 records from The South American spider genera Mesabolivar and Carapoia (Araneae, Pholcidae): new species and a framework for redrawing generic limits. 27 records from Collection Ephemeroptera - SMF. 645 records from Vertebrates (except birds, INNS and restricted records), Outer Hebrides. 7887 records from Données naturalistes d'Olivier GARGOMINY saisies sous cardObs. 79 records from ECOLINC: BIODIVERSITY OF THE WESTERN VOLCANIC PLAINS SIGHTINGS. 92433 records from Denver Museum of Nature & Science - Entomology. 3276496 records from Insecta of Costa Rica (INBio). 42 records from (Table 1) Abundance, wet biomass, and carbon biomass of all major groups of phytoplankton in the water column of the Kara Sea. 33748 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 16500 records from Database for alien invasive plants occurrences in Germany. 19 records from A new pygmy squid, Idiosepius hallami n. sp. (Cephalopoda: Idiosepiidae) from eastern Australia and elevation of the southern endemic ‘ notoides’ clade to a new genus, Xipholeptos n. gen.. 1348 records from Evaluación y monitoreo de manglar en la Reserva de la Biósfera Los Petenes con énfasis en criterios de sustentabilidad y desarrollo. 113 records from Tornoer Teich. 5 records from Revision of the soft scale genus Paralecanium (Hemiptera: Coccomorpha: Coccidae) with the introduction of three new genera and twenty new species. 71 records from Birdrace-NAJU_Aspach-Rems/Murr. 60 records from A revision of the grunter genus Syncomistes (Teleostei, Terapontidae, Syncomistes) with descriptions of seven new species from the Kimberley region, northwestern Australia. 7713 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 1151 records from Distribution of calcareous nannofossils from IODP Hole 313-M0027A. 671 records from Collection of Hymenoptera. 4372 records from Actualización e incremento del banco de datos de la colección de herbario del Jardín Etnobotánico de Oaxaca. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 459796 records from BioFokus. 10264 records from Anymals+plants - Citizen Science Data. 4677 records from DASSH Data Archive Centre volunteer sightings records. 16437 records from Arctic benthic invertebrate collection of the Zoological Institute of the Russian Academy of Science. 1 records from Glossing over cryptic species: Descriptions of four new species of Glossodoris and three new species of Doriprismatica (Nudibranchia: Chromodorididae). 24 records from Tauchen und Meer. 1 records from New or little-known taxa of Anurophorinae (Collembola) with anal spines from East Asia with notes on DNA barcode. 700 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2008. 376 records from Códigos de barras de helmintos de anfibios y reptiles de México. 85110 records from TTU Mammals Collection. 637 records from Inventaire de l'îlot du Lédénez Vraz. 62 records from Chenopodium vulvaria. 6 records from A new species of Stasimopus from the Eastern Cape Province of South Africa (Araneae, Mygalomorphae, Ctenizidae), with notes on its natural history. 37 records from City of Edinburgh Natural Heritage Service - Harperrig Otter Survey. 368 records from Ring ouzel national sample survey in the UK in 1999. 2240 records from (Figure 7) Distribution chart of benthic foraminifers in ODP Site 126-793. 1169 records from Red-throated diver national surveys in Scotland - raw data. 35 records from Phytoplankton abundance at station Sechin_2003-11-06_2, Casma, Peru. 14850 records from Données bibliographiques et opportunistes Mammifères issues du SiRF. 9 records from The genus Ctenomelynthus (Hemiptera: Heteroptera: Coreidae: Acanthocephalini), with the description of three new species and key to the known species. 131 records from BIRDRACE Brut. 617391 records from Données de la flore d’Alsace (SBA). 2 records from Description of a new species of Bothynus Hope from Argentina and Bolivia (Coleoptera: Scarabaeidae: Dynastinae). 150 records from Estudio de la variabilidad genética de Fundulus lima y sus relaciones filogeográficas con otros fundúlidos (Pisces: Fundulidae) de la Península de Baja California, México. 498 records from (Appendix 1) DSDP Site 94-607 ostracode species census data. 425 records from PAMP-tracheo: Vascular plants in La Demanda and Cameros mountain ranges (La Rioja, Spain). PhD project, L.M. Medrano. 72 records from Birdrace-Buteo2DO-Dortmund. 1 records from Cyrtodesmus baerti, n. sp., a cryptic millipede from the Galápagos Islands, Ecuador (Diplopoda, Polydesmida, Cyrtodesmidae). 1 records from Antarctic Krill occurrence data from Discovery expeditions. 264 records from (Table 4) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-847B. 1 records from Orthochaetes estrelanus sp. n., a new species from northern Portugal and new records of other Styphlini (Coleoptera, Curculionidae).. 4 records from Three new species of Lyssomanes HENTZ, 1845 from Peru (Arachnida: Araneae: Salticidae). 2 records from Updated checklist of Balearic leaf beetles (Coleoptera: Chrysomelidae). 479415 records from KTP Ring Data. 2 records from Two new species of Darnini (Hemiptera: Membracidae) from Colombia and Peru. 49 records from Données naturalistes (Rhopalocères et Zygènes) de Bob WHITMARSH (indépendant). 3715 records from Fungi and Lichens, Outer Hebrides. 496 records from Plant specimens of Oiso Municipal Museum. 3948 records from (Supplement 1) Relative abundance of planktic foraminifera in sediments of the last 560 kyr of ODP Hole 165-999A, Caribbean Sea. 1 records from Synthèse de la Répartition des populations de cerf élaphe en 2000 (réseau Ongulés sauvages ONCFS-FNC-FDC). 1021 records from Australian Institute of Marine Science (AIMS) - Lizard Island Reef Biodiversity Expedition, Queensland, Australia (2008 - 2009). 10 records from Unraveling Ocyptamus and the Baccha legacy (Diptera: Syrphidae): redefinition of groups and new species descriptions. 8 records from Three new species of seasonal killifishes of the Simpsonichthys antenori species group (Teleostei: Cyprinodontiformes: Rivulidae) from the rio São Francisco basin, Brazil.. 63 records from Range table from planktonic foraminifers in ODP Hole 139-858A. 162076 records from Mississippi Entomological Museum. 875 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 455 records from GERECO_Environnement_2017_12_18. 53 records from Schulgarten Fichteschule. 95 records from BIRDRACE accipiter hardcore birding. 18 records from On the taxonomy of southern South American species of the wolf spider genus Allocosa (Araneae: Lycosidae: Allocosinae). 890 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE262. 3424 records from LISU Herbario Angola. 4871 records from The Orthoptera collection (EO) of the Muséum national d'Histoire naturelle (MNHN - Paris). 73716 records from AM: Freshwater Invertebrates (1900-2005). 229 records from Distribución y estructura poblacional de la tortuga de Berlandier, (Gopherus [=Xerobates] berlandieri) en México. 466 records from Nannofossil abundance of Hole 4-31. 2057 records from Time slice 2 of planktic foraminifera of the last glacial maximum. 24 records from RNF - Données de la Réserve Naturelle du Marais de Lavours. 2 records from Description of two new species of the genus Automate De Man, 1888 (Crustacea: Decapoda: Caridea) from the South China Sea. 10 records from An inordinate fondness for Osedax (Siboglinidae: Annelida): Fourteen new species of bone worms from California. 1040 records from Foraminifera and ostracods profile from sediment core AV14_K2-3. 105 records from Revision of the Ephippiochthonius complex in the Iberian Peninsula, Balearic Islands and Macaronesia, with proposed changes to the status of the Chthonius subgenera (Pseudoscorpiones, Chthoniidae). 83 records from Records of Giant Silkmoths (Saturniinae) from Vermont Collections and 2002-2007. 5 records from A new Candonopsini (Ostracoda) genus from subterranean waters of New South Wales (Australia). 1824 records from TransForest vegetation data. 2 records from A remarkable new plant bug genus and species (Hemiptera, Heteroptera, Miridae, Deraocorinae) from the Australian wet tropics. 221 records from Systematics, distribution and biology of the Australian ' micro-flea' wasps, Baeus spp. (Hymenoptera: Scelionidae): parasitoids of spider eggs.. 201 records from Biodiversity of springs and rock seepages 2003. 35 records from Benthic foraminifera abundance of Hole 56-434. 1263 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina. 1775 records from NMU Mammal Collection (Arctos). 50 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 28 records from Black grouse lek survey in Moray and Nairn 2009. 5 records from A new genus and species of Sclerodactylidae (Echinodermata: Holothuroidea: Sclerothyoninae) from the Pacific coast of Panama, and assignment of Neopentamera anexigua to Sclerothyoninae. 768 records from Catalogue Lhomme 1923-[1963]. 521 records from Schanzenanlage Bergham. 140 records from Planktic foraminifera abundance of Hole 37-332. 396 records from (Appendix 1) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD95-2042. 48 records from Dörnberg. 88 records from The Crematogaster (Hymenoptera, Formicidae, Myrmicinae) of Costa Rica.. 20770 records from Herpetology Collection. 5037 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 2 records from Arthropoden aus südotsalpinen Höhlen gesammelt von Karl Strasser. 4. Aufsatz. 68 records from Bean geese on the Slamannan Plateau, Central Scotland between 1993 and 1995. 11 records from Southern distributional limits of Meliponini bees (Hymenoptera, Apidae) in the Neotropics: taxonomic notes and distribution of Plebeia droryana and P. emerinoides in Argentina. 909 records from Phytoplankton abundance and species composition in the Tyrrhenian Sea in November 1981. 61106 records from URM - Herbário Pe. Camille Torrand. 2 records from Macrozoque hoplandrioides (Coleoptera: Staphylinidae: Aleocharinae), a new genus and species of false Lomechusini from México. 123 records from Abundance of dead benthic foraminifera in sediment core CD86_06_BC5. 444 records from Marsabit Ecosystem Inventory Surveys 2014. 200 records from Range table from benthic foraminifers in ODP Hole 149-900A. 7715 records from ZMMU MSU, White Sea Branch. 1 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 32 records from Freshwater Gwyniad Survey Data. 18 records from Colección de Vertebrados (naturalizados y en fluido) del Departamento de Zoología de la Facultad de Biología de la Universidad de Sevilla. 27 records from Nannofossil abundance of Hole 10-85. 1052 records from Nannofossil abundance of Hole 37-334. 246 records from Rotifers of Macquarie Island. 57 records from Schulgelände SGD/Viersen. 2 records from The genus Thelepus Leuckart, 1849 (Annelida, Thelepodidae) in Brazil, with a redescription of the holotype of T. setosus (Quatrefages, 1866). 58 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 1303 records from Flora genérica de las gramíneas del estado de Tlaxcala. 1 records from Zur Kenntnis der Lithobiiden. 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 29 records from Revisionary systematics of the endemic soft coral fauna (Octocorallia: Alcyonacea: Alcyoniina) of the Agulhas Bioregion, South Africa. 10 records from Three species of Reteporella (Bryozoa: Cheilostomata) in a diapiric and mud volcano field of the Gulf of Cádiz, with the description of Reteporella victori n. sp. 5 records from Annelida specimens of Ryukyu University Museum (Fujukan). 9 records from A new record of Siler collingwoodi (Araneae: Salticidae) from Japan. 1180 records from Inventario herpetofaunístico del valle semiárido de Tehuacán-Cuicatlán. 4 records from Description of Rhamma dawkinsi (Lepidoptera: Lycaenidae) a new mountain butterfly from Colombia. 88 records from Meniscus Midges (Dixidae) of Ireland. 66 records from Revision Of The Spider Genus Neoanagraphis (Araneae, Liocranidae). 61 records from Photo images, 3D/CT data and mtDNA of the freshwater mussels (Bivalvia: Unionidae) in the Kyushu and Ryukyu Islands, Japan, with SEM/EDS analysis of the shell. 1 records from A new deep-sea species of the caridean genus Bresilia Calman, 1896 (Crustacea: Decapoda: Bresiliidae) from Sagami Bay, central Japan. 221 records from Mosquitoes (Culicidae) of Ireland. 3 records from Begonia elachista Moonlight & Tebbitt sp. nov., an enigmatic new species and a new section of Begonia (Begoniaceae) from Peru. 1498 records from Amphibians and reptiles of Ireland. 1 records from Description of a new species of the genus Agamura Blanford, 1874 (Squamata: Gekkonidae) from southern Iran. 603 records from Recursos hidrobiológicos de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia BIO. 224 records from Natura 2000 PnrL. 25066 records from UF Florida Museum of Natural History Mammals. 3401 records from Inventario florístico y base de datos de la familia Cucurbitaceae en México. 936 records from (Figure 3) Distribution chart of dinoflagellate cysts of Cretaceous age from ODP Hole 103-638B. 7 records from The genus Zelurus Hahn, 1826, in Brazilian caves: description of new species and comments on the potential distribution of the genus in South America. 6 records from One new species and two redescriptions of Marphysa (Eunicidae, Annelida) species of the Aenea-group from Australia. 40 records from Entomological collection of the National Museum. 144 records from BIRDRACE Punkbirder Helgoland. 50 records from Poliquetos litorales de la región norte y centro del estado de Veracruz. 277 records from Inventario de gasterópodos terrestres y dulceacuícolas del área focal de Ixcan, Chiapas. 19553 records from Coleoptera collection, NHM. 88651 records from Wicken Fen nature reserve species data held by The National Trust. 456 records from Range table from benthic foraminifers in ODP Hole 172-1057B. 50 records from Phytoplankton abundance at station Sechin_2003-12-28_2, Casma, Peru. 454 records from SEWBReC Lacewings and Allies (South East Wales). 231 records from UWIZM International Lepidoptera Collection. 1726 records from Helmintos parásitos de peces del sureste de México. 1652 records from Proyecto de cultivo extensivo y comercialización de las mariposas de la región de Chajul, Chiapas. 61 records from Naturpark Kottenforst-Ville 15.6.09. 418 records from Radiolaria assemblage in sediment core GIK23259-2. 246 records from Araignées PNRL-2010 (Troyon,Jezainville-pelouse, Genicourt-pelouse). 1134 records from Alterra (NL) - Microarthropods inventory in European countries. 41 records from New species and new records of gelechiid moths (Lepidoptera, Gelechiidae) from southern Siberia. 4 records from Range table from benthic foraminifers in ODP Hole 194-1193A. 63 records from Total foraminifera counts of multinet M21/4_MSN706. 2 records from New species of Poecilocloeus Bruner, 1910 (Orthoptera: Acrididae: Proctolabinae) from Paraná State, Brazil. 294 records from Distribution of calcareous foraminifers in sediment core Well 6407/9-3. 173 records from FFH-Gebiet Klosterwasser/Burkau. 6556 records from (Appendix 2) Distribution of generalized biologic, anthropogenic, and volcanic constituents in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 620 records from GNOR-Projekt "Halbwilde Weidehaltung zwischen Kamp-Bornhofen und Kestert" und Umland. 36 records from Abundance of benthos infauna at station GIK23043-2. 100 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 40166 records from Staffordshire Wildlife Trust Nature Reserves Inventory. 4226 records from Collection Pisces SMF. 1 records from The identity of Cicinnus orthane Blanchard, 1852 (Lepidoptera, Mimallonidae, Cicinninae), type species of Cicinnus Blanchard, 1852. 286 records from (Figure 2) Distribution chart of dinoflagellate cysts of Cretaceous age from ODP Hole 103-638C. 384 records from MEXU/Tipos de plantas vasculares. 2120 records from Freshwater Pest Plants. 272652 records from Florida Keys Reef Visual Census 2007. 27 records from Redescription of Bomis larvata L. Koch, 1874 with the description of a new Australian species. 1613 records from Biodiversidad asociada a mantos de rodolitos y praderas de pastos marinos en Bahía Concepción, BCS. 15 records from Ctenodontina Enderlein, 1914 (Diptera, Asilidae, Asilinae): new combinations, synonyms, new species and new records for Argentina. 852 records from Range table from planktonic foraminifers in ODP Hole 139-857A. 7735 records from Abundances indices and biological traits of juvenile salmon sampled in the Oir river (France). 240 records from Landschaftspflegehof (Berlin). 9 records from Bachpatenschaft Beeke. 5366 records from City of Edinburgh Natural Heritage Service - Bavelaw Marsh Bird Hide Records. 390 records from (Fig. 8g-h, 11) Abundance of planktonic foraminifera and estimation of sea surface temperature and export production of sediment core MD95-2040. 61 records from Review of the genus Eopompilus Gussakovskij, 1932 (Hymenoptera: Pompilidae) with the description of new species from China. 165 records from Artenvielfalt auf den Elbwiesen (Dessau). 1009 records from Données naturalistes de Daniel PAVON. 2 records from Two new species of Dactylonotus Parent, 1934 (Diptera: Dolichopodidae) from South Africa and a key to Afrotropical species. 19 records from Inventario de Aves Pauto J, Yopal, Casanare. 3 records from Two new species of the genus Cataglyphis Foerster, 1850 (Hymenoptera: Formicidae) from Iran.. 92 records from Anfibios y reptiles de la desembocadura del caño Teracay en el río Tomo, Puerto Carreño, Vichada - Proyecto Colombia Bio. 6 records from Nannofossil abundance of Hole 31-298A. 93925 records from Diversidade e ocorrência de peixes em Inhambane (2009-2017). 2340 records from (Figure 10) Range chart of selected dinocysts and acritarchs of ODP Hole 104-644B. 174 records from (Table A.08) Foraminiferal census data of sediment core PS1243-1 during marine isotopic stage 1-3 (80-150 µm). 529 records from Superórden Dictyoptera del Museo de Entomología de la Universidad del Valle (Cali, Colombia). 1329 records from Echinoderm specimens of Ryukyu University Museum (Fujukan). 1 records from Description of a new species of Lutosa Walker, 1869 (Orthoptera: Anostostomatidae: Lutosinae) from the Brazilian Atlantic Forest, with biological and behavioral information. 31 records from Phytoplankton abundance in surface water in 2004, Ancon, Peru. 17 records from Comunidad de Herpetos presentes en el río Tutunendo, Municipio de Quibdó-Chocó. 4159 records from DBG Mirabilis rotundifolia Demographic Monitoring. 5910 records from The molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from Synthèse de la Répartition des populations de cerf élaphe en 1995 (réseau Ongulés sauvages ONCFS-FNC-FDC). 3 records from To the knowledge of Oriental species of subgenus Pseudochlaeniellus Jeannel, 1949 (Coleoptera, Carabidae, Chlaenius). 367 records from ARKO. 2270 records from Esponjas, corales escleractinios, equinodermos y peces de arrecifes coralinos del norte y sur de Veracruz. 70788 records from Atlas of Life in the Coastal Wilderness - Sightings. 1738 records from Gipuzkoako Foru Aldundiaren Landareen Germoplama Bankua / Banco de Germoplasma Vegetal de la Diputación Foral de Gipuzkoa. 172 records from Nannofossil abundance of Hole 49-412. 1 records from Coeliccia rolandorum sp. nov. from eastern Cambodia and southern Vietnam, the eastern relative of C. kazukoae Asahina, 1984 (Odonata: Platycnemididae). 26 records from Abundance of benthos infauna at station PS1240-1. 8922 records from Records of the Queensland Plant Pathology Herbarium. 8 records from A review of the Arcuphantes species with the genitalia of arcuatulus - type (Araneae, Linyphiidae). 823 records from Amphibia collection of the Museu Nacional de História Natural e da Ciência, Universidade de Lisboa, Portugal. 61 records from Amphipoda Hyperiidea of the Southern Ocean: catalogue and occurrences. 49 records from Amphibian specimens of Kanagawa Prefectural Museum of Natural History. 94 records from Birdrace-Erlanger_Piepmätzchen-Erlangen/Höchstadt. 1135 records from MarineGEO visual diver surveys of fish communities around Carrie Bow Cay, Belize, 2015. 72 records from Polish seed gene bank – historical passport data of accessions. 64 records from Westerwälder Umwelt- und Naturschutztag an der Fuchskaute im Westerwald. 3 records from A new species of Misetus Wesmael, 1845 (Hymenoptera, Ichneumonidae, Ichneumoninae, Phaeogenini) from Italy, with updated key to the females of Palaearctic species. 895 records from Coleção de Ictiologia do Museu de Ciências Naturais da Universidade do Vale do Taquari - Univates (ZIUMCN-UNIVATES). 6 records from Nine new Trechisibus species from Peru and Argentina (Coleoptera: Carabidae: Trechinae). 11209 records from Colección Herpetológica "Lic. Blanca Beatriz Alvarez" - Facultad de Ciencias Exactas y Naturales y Agrimensura - Universidad Nacional del Nordeste. 3063 records from Données entomologiques sur la Réserve Naturelle de l’Étang Noir. (Seignosse, Landes). Bilan des études 2001 à 2009. 2 records from Hildener Heide - Spörkelnbruch (Haan). 1446 records from Peces y Mamíferos de la región de Norogachi, Alta Sierra Tarahumara, Chihuahua. 5406 records from Données Lépidoptères de l'Auvergne transmises par Pascal Peyrache.. 17 records from Descriptions, transference and new records of Lamiinae from Central and South America (Coleoptera, Cerambycidae). 1037 records from Patrones de variación espacial y temporal de la biodiversidad fitoplanctónica de los cenotes abiertos de Yucatán. 6 records from New Black Fungus Gnats (Diptera, Sciaridae) of North America. Part IV. Genera Eugnoriste Coquillett and Keilbachia Mohrig. 65804 records from University of British Columbia - Spencer Entomological Collection (UBCZ). 33182 records from La colección briológica del Herbario Nacional (MEXU). Actualización 2000. 351 records from Küstenschutzwald. 48044 records from Fiocruz/CMN - Coleção de Mosquitos Neotropicais. 2574 records from The Diatom Collection of Franz Josef Weinzierl at the Botanische Staatssammlung München. 134 records from BIRDRACE Griffin Wood Warblers. 19266 records from Herbário da Pontifícia Universidade Católica do Paraná - HUCP. 45 records from Range table from benthic foraminifers in ODP Hole 146-891A. 17 records from Inventarios de Herpetos de la Microcuenca de la Quebrada Agua Blanca, Vereda Marroquín, Yopal, Casanare. 432 records from Fishes in MZNA-VERT: ecological assessment of the Guadalope river in Aliaga (Spain). 76 records from Phytoplankton abundance and species composition in the North Balearic Sea in April 2003. 4 records from Planktic foraminifera abundance of Hole 54-424. 2 records from The Muscidae (Diptera) of Armenia. 1 records from Redescription and lectotype designation of Chasmogenus abnormalis (Sharp), with notes on its distribution. 17540 records from Museu de Ciències Naturals de Barcelona: MCNB-Cord. 45 records from SNH Invertebrate Site Condition Monitoring of Beetle Assemblage Features 2015: Fannich Hills SSSI. 1748 records from Distribución potencial del género Ficus (Moraceae) en México. 1215 records from (App 4) Relative contents of benthic foraminifera species in Holocene sediments from Core BP00-07/05. 60413 records from Derek Lott Coleoptera Dataset. 2 records from Données de Lépidoptères de Bruno DAUGET - Dépt des PYRENEES-ORIENTALES (66). 1520 records from (Table 16) Benthic foraminifera in Eocene-Oligocene sediments of DSDP Hole 90-593. 2048 records from PACA-Fungi - Herbarium Anchieta - Fungi Rickiani. 2665 records from PINK - Dragonfly (Odonata) monitoring for the permanent surveillance of coastal areas in Flanders, Belgium. 7158 records from University of Alberta Museum of Zoology Ichthyology Collection (UAMZ). 7 records from A new species of poison-dart frog (Anura: Dendrobatidae) from Manu province, Amazon region of southeastern Peru, with notes on its natural history, bioacoustics, phylogenetics, and recommended conservation status. 353 records from Données naturalistes de Hubert GUIMIER. 2646 records from (Table 3) Stratigraphic distribution of dinocyst taxa in ODP Hole 150-903C. 1728 records from Collection rousset -1947-2013. 1860 records from Données naturalistes de Hervé BOUYON. 4214 records from Naturhistorisches Museum Mainz, Schmetterlingssammlung Rodenkirchen. 152 records from Wildkräuter. 386 records from Thistle Heads and Ermerged Insects. 294 records from Données naturalistes de BALLUCK Cindy. 101 records from Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae). 192 records from Berlin-Brandenburg Plant Collection 2004. 1201 records from Centro de Recuperación de Fauna Silvestre "La Tahonilla". Cabildo de Tenerife. 55 records from Vegetationsmatrix schorfheide alb 2008 durchgang2. 152 records from Total foraminifera counts of multinet POS247/2_MSN1372. 16767 records from Hokkaido University Coleoptera Collection. 11 records from New species of Bacuma Cameron (Hymenoptera: Braconidae: Braconinae) from Kenya and West Darfur with a key to species. 48 records from Artenerfassung für Jedermann in der Grundschule Kirchboitzen. 270 records from Registros biológicos de aves Distrito de Manejo Integrado Musichi y Santuario de Fauna y Flora los Flamencos, La Guajira.. 755 records from Freiburger GEO-Tag der Artenvielfalt. 757 records from Pseudoscorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 3 records from Description of a new species of Euptychiina (Lepidoptera: Nymphalidae: Satyrinae) from South America. 9052 records from Highland bird data 2002 - 2003 - non-breeding records. 350 records from Estudio de la estructura genética espacial de la palma Elaeis oleifera. 19923 records from UMNH Birds Collection (Arctos). 6 records from Inventaire de la flore des espaces verts de la CREA avec le protocole Florilèges. 18 records from Range table from planktonic foraminifers in ODP Hole 182-1129B. 4158 records from RNF - Données du Parc Naturel Régional du Vercors. 45 records from Crustacea specimens of Kuroshio Biological Research Foundation. 1377 records from RECORD Freshwater Fish Data. 2993 records from Insectes Hyménoptères Scollidés de France. 18 records from GEO-Tag der Artenvielfalt der Klasse 7c am Gymnasium Allee im Wohlers Park. 1555 records from (Table 2) Relative abundances of benthic foraminifera in ODP Hole 128-798B. 250 records from Colección de Mamíferos – Universidad de la Amazonia. 320 records from Counts of benthos communities in Kongsfjorden in 2009. 363 records from IOW Natural History & Archaeological Society Marine Records. 6190 records from Fauna y flora en áreas con cultivos de palma de aceite en el norte y oriente de Colombia. 131373 records from UAM Mammal Collection (Arctos). 14 records from Données naturalistes de Piotr DASZKIEWICZ. 71 records from Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010. 28 records from Afroneutria, a new spider genus of Afrotropical Ctenidae (Arachnida, Araneae). 221 records from Caracterización florística de las ciénagas en Gamarra y Barrancabermeja de 2012. 2528 records from Communauté_de_communes_Asse_Bléone_Verdon_2017_12_18. 48 records from Nanofaunaartenliste. 19692 records from Base de datos de la distribución de la flora de la Reserva de la Biosfera Tehuacán-Cuicatlán. 135 records from Waldi-Weiher. 1040 records from Composition of planktonic foraminifera species from 310 sediments samples during the last glacial maximum. 210 records from (Table 1) Distribution of foraminifera in the Miocene section of ODP Hole 133-815A. 459 records from Gewann Krampf (Heilbronn). 114 records from The jumping lynx spider Oxyopes salticus Hentz, 1845 and its Neotropical relatives (Araneae: Oxyopidae). 1077 records from Fishes of the Congo River 2010 Expedition. 3 records from On new or poorly known Australian Filistatidae spiders (Araneae: Araneomorphae), including a study on the fine morphology of Wandella. 74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 1 records from Synthèse de la Répartition des populations de cerf élaphe en 1988 (réseau Ongulés sauvages ONCFS-FNC-FDC). 52 records from Biología reproductiva de Hechtia schottii Baker ex Hemsley (Bromeliaceae), una especie dioica y rara de la Península de Yucatán. 64 records from Distribution of less-numerous macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 4). 406 records from Pollen profile from Muscotah Marsh B. 1390 records from Distribution of planktic foraminifera and stable istopes of sediment core MSM05/5_712-2. 120 records from (Table 10) Occurrence of benthic foraminifera in ODP Hole 112-688E, Part II. 15 records from Range table from planktonic foraminifers in ODP Hole 182-1129A. 3312 records from Algae, Specimens, Agder naturmuseum (KMN). 80 records from (Table 2) Relative abundances of shallow-water foraminifera in ODP Hole 133-821A. 3 records from Revision of Terellia amberboae group of species (Diptera: Tephritidae). 1343 records from Florística y biogeografía de algunos bosques mesófilos de la Huasteca Hidalguense: Fase 3 (Chapulhuacán y Pisaflores). 156 records from SNH Invertebrate Site Condition Monitoring 2013/14: Earlshall Muir SSSI. 5 records from A New Southern Caribbean Species of Angel Shark (Chondrichthyes, Squaliformes, Squatinidae), Including Phylogeny and Tempo of Diversification of American Species. 12254 records from The Araneae Collection of the National Museum of Nature and Science. 157 records from Planktic foraminifera counts at CTD station PS55/078-1. 355 records from (Table 2) Species density and composition of an inshore and offshore station in Kongsfjord, Svalbard. 4 records from Determinación de la clase Reptilia presente en el corregimiento de Juanchaco, Valle del Cauca, Colombia para el mes de Septiembre de 2017. 185 records from Dinoflagellate cysts from sediment core PS2741-1. 79 records from Birdrace-Bielefinken-Bielefeld. 107 records from Müritz-Nationalpark. 913 records from Phytoplankton abundance in surface water in October 1997, Pisco, Peru. 5999 records from Colección Limnológica Universidad de Antioquia. 146 records from Birdrace-Wannacks_Topti(c)ker-Lübeck. 180 records from Spécimens d'herbiers de G. Fenoul (FEN). 270 records from Wald am Schloss Wittgenstein Bad Laasphe. 544 records from Museo Provincial de Ciencias Naturales “Dr. Ángel Gallardo”, Rosario, Argentina - Colección Peces (MG-ZV-P). 328987 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 168 records from Assemblage of living benthic foraminifera in sediment core GeoB4916-4. 66 records from Australian Diplectroninae reviewed (Insecta: Trichoptera), with description of 21 new species, most referred to a new genus. 113941 records from Pacific Ocean Shelf Tracking (OBIS Canada). 570 records from Relative abundances of middle Pleistocene benthic foraminifera in DSDP Site Site 90-594. 7623 records from Base de datos de las gramíneas (Poaceae) del noreste de México. 173 records from Renaturierung Werse (Innenbereich Beckum). 23 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1a. 1561 records from Abundance of benthic infauna in surface sediments from the North Sea sampled during cruise Dana00/5. 52534 records from FUEL - Herbário da Universidade Estadual de Londrina. 4036 records from Inventario de larvas de peces en la región sur del Golfo de California (GAP 81, 85 y 86) y en el Pacífico Tropical Mexicano (GAP 88-91). 73830 records from UTEP Plants (Arctos). 10726 records from Dragonfly (Odonata) species records up to 1997 held by Leicestershire Environmental Resources Centre. 58 records from The cicada genus Procollina Metcalf, 1952 (Hemiptera: Cicadidae): redescription including fourteen new species, with a key to the species of the subtribe Dazina Kato, 1932 rev. stat., the description of the Aragualnini n. tribe, and one new combination. 5 records from Composition of the fine silt fraction in surface sediments of the northwest African continental margin (Appendix Tab. 4). 80 records from Range table from planktonic foraminifers in ODP Hole 139-855A. 247 records from Abundance of large foraminifera in cores from transect NOG-01B, IODP Expedition 325. 666 records from Macroinvertebrate abundance in montane tropical streams of varying land-use, Ecuador. 53 records from Bad Bodenteicher Heide. 3 records from ALERT Non-Native Species Records for Signal Crayfish. 88 records from Ober-Olmer Wald 09. 444 records from South Lanarkshire peatland records 2013. 39 records from Inventaire des oiseaux sur le territoire de la métropole Rouen Normandie. 2673 records from PondNet data 2012-2014. 44 records from Planktic foraminifera abundance of Hole 63-472. 2343 records from Museo Nacional de Ciencias Naturales, Colección de Aves: MNCN-Ornit. 1342 records from Derbyshire Casual LEPIDOPTERA records - Casual records collated by Derby Museum.. 706981 records from Finnish monitoring scheme of birds and mammals visiting bird feeders during winter. 71813 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 15172 records from Universidad Autónoma de Madrid, Madrid; Lepidópteros. 1158 records from Algaterra Types. 1 records from Cepolacanthus kimi, a new genus and species of copepod (Cyclopoida: Taeniacanthidae) parasitic on Bandfish Acanthocepola abbreviata (Valenciennes, 1835) (Actinopterygii: Cepolidae) caught off the Iraqi coast. 194576 records from Fungi (S). 1 records from Données naturalistes de Frédéric JARRY. 13020 records from Données de l'atlas des Mammifères sauvages de Midi-Pyrénées (données agrégées à la maille de 10km). 2762 records from Alien macro-invertebrates in Flanders, Belgium. 1905 records from Black grouse annual lek surveys in Dumfries and Galloway, 1980-2011. 141 records from Computarización de la colección de myxomycetes y líquenes de Baja California. 28256 records from NCSM Mollusks Collection. 15 records from Naturschutzgebiet Ahrschleife (Altenahr). 1054 records from Situación actual de ocho especies de anfibios en categoría de riesgo en Veracruz. 368 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 88 records from Great Crested Newt Special Area of Conservation (SAC) Monitoring Data. 1966 records from ZUEC-ARA - Coleção de Aracnideos do Museu de Zoologia da UNICAMP. 4309 records from Données naturalistes de Ségolène FAUSTEN. 62 records from Distribución, abundancia y efectos nocivos de tres especies de plantas invasoras. 81044 records from PACA-AGP - Herbarium Anchieta. 6250 records from Natural History Museum Maastricht (NL) - Herbarium. 59695098 records from Artportalen (Swedish Species Observation System). 461 records from Range table from planktonic foraminifers in ODP Hole 182-1134A. 403 records from Range table from benthic foraminifers in ODP Hole 181-1119C. 2 records from Microlepidogaster negomata, a new hypoptopomatine catfish (Loricariidae: Hypoptopomatinae) from Rio São Francisco basin, southeastern Brazil. 10 records from Description of three new troglobiontic species of Cybaeodes (Araneae, Liocranidae) endemic to the Iberian Peninsula. 65 records from Other Arachnida collection of National Museum of Nature and Science. 500 records from Collection of Coleoptera. 72 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 1 records from Karpfenteich, Klasse 6d. 6 records from Range table from planktonic foraminifers in ODP Hole 145-883C. 24 records from Nematode genera abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/324-1. 8753 records from Vascular Plants Collection of National Museum of Nature and Science. 11 records from A new species of Sextonia Chevreux, 1920 (Crustacea: Amphipoda: Liljeborgiidae) from the Okhotsk Sea. 30416 records from Canada Maritimes Regional Cetacean Sightings (OBIS Canada). 2 records from List of the specimens of the Vanuatu National Herbarium (PVNH). 15 records from Monitoreo de Murciélagos en la Etapa de Ejecución de las Obras de Ampliación del EPF Floreña, Yopal, Casanare. 6805 records from SEWBReC Grasshoppers, Bush-crickets and allies (South East Wales). 2 records from Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa. 44 records from Planktic foraminifera abundance of Hole 40-361. 17 records from Hypostomus velhochico, a new keeled Hypostomus Lacépède, 1803 (Siluriformes: Loricariidae) from the rio São Francisco basin in Brazil. 2 records from Description of a new catfish, Silurus tomodai (Siluriformes: Siluridae) from central Japan. 584442 records from Queensland Museum provider for OZCAM. 10123 records from Bruce Bennett Herbarium (BABY). 417 records from Loup 2016 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 71 records from Range table from planktonic foraminifers in ODP Hole 182-1133C. 119 records from (Table 5) Planktonic foraminifera genera assemblage at DSDP Hole 80-548A. 192 records from (Table 3) Absolute concentrations and raw counts of seven genera of dinoflagellate in ODP Site 170-1039. 11 records from Proposal of Kupiuka and Plesiopiuka, two new genera of jumping spiders from Brazil (Araneae: Salticidae: Heliophaninae). 708 records from EDP Baixo Sabor: Herpetology – Baseline Studies [2009]. 1 records from Molche in Ruschwedel. 2 records from Review of the Madagascan Orphninae (Coleoptera: Scarabaeidae) with a revision of the genus Triodontus Westwood. 895 records from Códigos de barras de hongos ectomicorrízicos de localidades selectas del neotrópico mexicano. 10944 records from Danish Plant Bugs (Miridae). 6 records from The genus Setodes Rambur (Trichoptera, Leptoceridae) in Japan. 31 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 1998. 18326 records from ZUEC-POL - Coleção de Polychaeta do Museu de Zoologia da UNICAMP. 107 records from Range table from benthic foraminifers in ODP Hole 146-889B. 43292 records from Données naturalistes d'Olivier ESCUDER. 57 records from Morphology and taxonomy of the orb-weaving spider genus Mecynogea, and a peculiar species of Argiope (Araneae, Araneidae). 8 records from A review of New World Malaxa (Hemiptera: Fulgoroidea: Delphacidae). 701 records from Données naturalistes d'Arnaud LE NEVÉ. 2147 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 6077 records from Vascular plant specimens of Iida City Museum. 39 records from Nannofossil abundance of Hole 16-155. 20167 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 111 records from Nematode densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC02. 717 records from Redland City Council Citizen Science Portal. 2 records from Revision of early taxa of Australian gall midges (Diptera: Cecidomyiidae). 239 records from Caracterización de algas y comunidad íctica de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 311 records from HBRG Invasive Non-native Plants Dataset. 163 records from Steinbruch Mainz-Weisenau, 3. Jahr. 1532 records from Museu Paraense Emílio Goeldi - Carcinológica Collection. 3251 records from Inventario florístico de la Sierra de Huautla, Morelos. 3 records from Revision of the genus Centrophorus (Squaliformes: Centrophoridae): Part 2 - Description of two new species of Centrophorus and clarification of the status of Centrophorus lusitanicus Barbosa du Bocage & de Brito Capello, 1864. 166 records from Zielbach (Töll). 96 records from BIRDRACE Emslandracer. 851 records from Pollen profile V and Ausfluss at Krumbach, Germany. 525 records from Inventario de sanguijuelas (Annelida: Clitellata Hirudinea) de México, con énfasis en las especies del centro de México. 2109 records from SEWBReC Worms (South East Wales). 229 records from Queen Charlotte Sound / Tōtaranui and Tory Channel / Kura Te Au (HS51) Hydrographic Survey Marine Mammal Observations. 127113 records from University of Michigan Museum of Zoology, Division of Reptiles & Amphibians. 5 records from Two new species of Guyruita Guadanucci et al., 2007 (Araneae, Theraphosidae) from Brazil. 3 records from New species of Graphocaecilius Enderlein (Psocodea: ‘ Psocoptera’: Lachesillidae) from Colombia. 104636 records from University of Michigan Museum of Zoology, Division of Mammals. 19587 records from Birds Specimens. 45880 records from Banco de datos florísticos del Herbario CHAP. 58 records from Schulgelände Kranich-Gymnasium (Salzgitter). 23 records from Record of 7 acritarch taxa from the Miocene, Pliocene and Pleistocene of ODP Hole 151-910C. 1 records from Contributions to the study of Idiocerinae (Homoptera: Auchenorrhyncha: Cicadellidae) of Central Asia with notes on synonymy. 1 records from Redescription of Micaria beaufortia (Araneae, Gnaphosidae), with notes on Afrotropical Micaria. 1594 records from Angelo State Natural History Collections (ASNHC) - Ornithology Collection. 9264 records from Big Island Invasive Species Committee - Pest Reports - 2005-2010. 4337 records from Données CardObs (hors programme spécifique). 86 records from Fliegenhaupt Marksuhl. 80 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 17886 records from DMNS Mammal Collection (Arctos). 6200 records from Bird collection NTNU University Museum. 1888 records from Back from the Brink vascular plant species abundance and distribution for Great Britain for the period 2002-2009. 6642 records from Akita Prefectural Museum, Hiroki Watanabe Collection. 97 records from Newhaven Sanctuary observations. 787 records from Relative abundance of adult opstracoda shells of surface sediment samples from the Persian Gulf (Table 1b). 1 records from Review of the ant genus Nesomyrmex (Hymenoptera: Formicidae: Myrmicinae) in southern Africa.. 1052 records from IBF Monitoring of Fungi. 59 records from Flora del Bosque de los Guayupes Acacias, Meta, Colombia. 26072 records from Herbario Pontificia Universidad Javeriana. 2242 records from (Table 3) Distribution of planktonic foraminifera in the early Cretaceous and early Eocene to late Oligocene sections of ODP Hole 149-897C. 119 records from Programme de valorisation des zones humides chassées - volet Amphibiens. 3018 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo de Páramos Pisba, Boyacá. 1 records from The genus Cryptotendipes Beck et Beck in Florida, with the description of a new species (Diptera: Chironomidae: Chironominae). 100 records from (Figure 5) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 103-640A. 4780 records from Données de la collection d'ichtyologie du MNHN (GICIM). 1 records from A new genus and species of Laelapidae (Acari: Mesostigmata) from Iran. 1 records from A new species of Ascidiacea (Herdmania andamanensis sp. nov.) from Andaman and Nicobar Islands, India. 1736 records from Siembras para restauración en La Mojana. 53 records from Données 2017 de l'Observatoire de la Biodiversité des Forêts. 7 records from A review of Newportia species in the subgenus Newportides Chamberlin, 1921 (Scolopendromorpha, Scolopocryptopidae, Newpo
Keywords: GBIF; biodiversity; species occurrences